Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal element, and method for producing liquid crystal element

The liquid crystal aligning agent with specific compounds improves substrate adhesion and film stability, addressing peeling issues in liquid crystal elements under harsh conditions and maintaining display quality.

JP7605065B2Active Publication Date: 2024-12-24JSR CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021133363
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-19
Filing Date
2021-08-18
Publication Date
2024-12-24
Estimated Expiration
2041-08-18

AI Technical Summary

Technical Problem

Liquid crystal alignment films tend to peel off from substrates under harsh environmental conditions, such as high temperature and high humidity, leading to deteriorated display quality in liquid crystal elements.

Method used

A liquid crystal aligning agent containing a polymer component and specific compounds represented by formulas (1) and (2), which enhance adhesion to the substrate and improve film stability.

Benefits of technology

The solution results in a liquid crystal alignment film with enhanced adhesion to the substrate, maintaining display quality even under harsh conditions and supporting high voltage holding characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605065000001
    Figure 0007605065000001
  • Figure 0007605065000002
    Figure 0007605065000002
  • Figure 0007605065000003
    Figure 0007605065000003
Patent Text Reader

Abstract

To provide a liquid crystal alignment agent capable of improving adhesiveness of a film to a substrate.SOLUTION: A liquid crystal alignment agent contains: a polymer component; and a compound [A] to be at least one kind selected from a group composed of a compound represented in formula (1) and a compound represented in formula (2). In the formula (1), Y1 and Y2 are hydrogen atom or a monovalent organic group. Z1 is a (c+d)-valent organic group satisfying (i), (ii) or (iii): (i) a (c+d)-valent group whose carbon number is 1 to 8 where at least one methylene group of a saturated chain hydrocarbon group is replaced by -O-; (ii) a (c+d)-valent saturated hydrocarbon group or the like whose carbon number is 11 or larger; and (iii) -S-, -SO2- or -CO-. In formula (2), at least one of Y3, Y3 of Y4, and Y4 is a monovalent group represented by one of formula (Y-1) to formula (Y-6).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal aligning agent, a liquid crystal alignment film, a liquid crystal element, and a method for producing a liquid crystal element. [Background technology]

[0002] A liquid crystal element has a liquid crystal alignment film that has the function of aligning liquid crystal molecules in a liquid crystal layer in a certain direction. A liquid crystal alignment film is generally formed on a substrate by applying a liquid crystal alignment agent, which is a polymer component dissolved in an organic solvent, to the substrate surface and preferably by heating.

[0003] In recent years, large-screen, high-definition liquid crystal televisions have become mainstream, and small display terminals such as smartphones and tablet PCs have become more widespread, so that the demand for higher quality liquid crystal elements is higher than ever before. Therefore, various liquid crystal alignment agents have been proposed in order to improve the performance of liquid crystal alignment films and to improve various properties of liquid crystal elements (see, for example, Patent Document 1). Patent Document 1 discloses that a compound having a structure in which a methylol group is bonded to an aromatic ring is contained in a liquid crystal alignment agent together with a polyimide or a polyimide precursor. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2010 / 074269 Summary of the Invention [Problem to be solved by the invention]

[0005] Liquid crystal elements are not only used in display terminals such as personal computers as in the past, but are also used in a wide variety of applications, both indoors and outdoors, such as liquid crystal televisions, car navigation systems, mobile phones, smartphones, information displays, retardation films, and light control films. In addition, as the applications of use expand, liquid crystal elements are expected to be used in harsher environments than before. For example, liquid crystal elements may be irradiated with a backlight for a long time due to continuous driving for a long time, or may be used in a high-temperature and high-humidity environment. In addition, the use of liquid crystal elements in harsh environments makes the liquid crystal alignment film more likely to peel off from the substrate. On the other hand, if the liquid crystal alignment film peels off from the substrate, there is a concern that the display quality of the liquid crystal element may be reduced.

[0006] The present invention has been made in consideration of the above problems, and has as its main object to provide a liquid crystal aligning agent capable of improving the adhesion of a film to a substrate. [Means for solving the problem]

[0007] According to the present invention, the following means are provided. [1] A liquid crystal aligning agent comprising a polymer component and at least one compound [A] selected from the group consisting of compounds represented by the following formula (1) and compounds represented by the following formula (2): [ka] (In formula (1), Y 1 and Y 2 are each independently a hydrogen atom or a monovalent organic group. 1 and X 2 are each independently a hydroxyl group, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. a1 and a2 are each independently an integer of 1 to 3. b1 and b2 are each independently an integer of 0 to 3, provided that 1≦a1+b1≦5 and 1≦a2+b2≦5 are satisfied. Z 1 is a (c+d)-valent organic group that satisfies the following (i), (ii), or (iii): (i) a (c+d)-valent group having 1 to 8 carbon atoms in which at least one methylene group of a saturated chain hydrocarbon group is replaced with -O-, a (c+d)-valent group having 1 to 8 carbon atoms in which at least one hydrogen atom of a saturated chain hydrocarbon group is replaced with a fluorine atom and at least one methylene group of the saturated chain hydrocarbon group is replaced with -O-, or a (c+d)-valent group having 2 to 8 carbon atoms in which at least one hydrogen atom of a saturated chain hydrocarbon group is replaced with a carboxyl group. (ii) A (c+d)-valent saturated hydrocarbon group having 11 or more carbon atoms, or a (c+d)-valent aromatic hydrocarbon group having 7 or more carbon atoms. (iii) -S-, -SO2- or -CO-. c and d are each independently an integer of 1 to 3. However, in the case of (iii) above, c+d=2. Y 1 , Y 2 , X 1 and X 2 When the same symbol is present multiple times in the formula, the groups having the same symbol are the same or different from each other. [ka] (In formula (2), Y 3 and Y 4 are each independently a hydrogen atom or a monovalent organic group. 3 and Y 4 At least one of X is a monovalent group represented by any one of the following formulas (Y-1) to (Y-6). 3 and X 4 are each independently a hydroxyl group, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. a3 and a4 are each independently an integer of 1 to 3. b3 and b4 are each independently an integer of 0 to 3, provided that 1≦a3+b3≦5 and 1≦a4+b4≦5 are satisfied. Z 2 is an organic group having a valence of (e+f). e and f are each independently an integer of 1 to 3. Y 3 , Y 4 , X 3 and X 4When the same symbol is present multiple times in the formula, the groups having the same symbol are the same or different from each other. [ka] (In formulas (Y-1) to (Y-6), R a and R b are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. "*" indicates a bond.)

[0008] [2] A liquid crystal alignment film formed using the liquid crystal alignment agent according to [1] above. [3] A liquid crystal element comprising the liquid crystal alignment film according to [2] above. [4] A method for manufacturing a liquid crystal element, comprising: a step of applying the liquid crystal alignment agent according to [1] above onto each conductive film of a pair of substrates having a conductive film to form a coating film; a step of constructing a liquid crystal cell by disposing the pair of substrates coated with the liquid crystal alignment agent so that the coating films face each other across a liquid crystal layer; and a step of irradiating the liquid crystal cell with light while a voltage is applied between the conductive films.

[0009] [5] A compound represented by the following formula (1): [ka] (In formula (1), Y 1 and Y 2 are each independently a hydrogen atom or a monovalent organic group. 1 and X 2 are each independently a hydroxyl group, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. a1 and a2 are each independently an integer of 1 to 3. b1 and b2 are each independently an integer of 0 to 3, provided that 1≦a1+b1≦5 and 1≦a2+b2≦5 are satisfied. Z 1is a (c+d)-valent group having 2 to 8 carbon atoms in which at least one hydrogen atom of a saturated chain hydrocarbon group has been substituted with a carboxyl group, or a (c+d)-valent group having 1 to 8 carbon atoms in which at least one hydrogen atom of a saturated chain hydrocarbon group has been substituted with a fluorine atom and at least one methylene group of the saturated chain hydrocarbon group has been replaced with -O-. c and d are each independently an integer of 1 to 3. Y 1 , Y 2 , X 1 and X 2 When the same symbol is present multiple times in the formula, the groups having the same symbol are the same or different from each other.

[0010] [6] A compound represented by the following formula (2): [ka] (In formula (2), Y 3 and Y 4 are each independently a hydrogen atom or a monovalent organic group. 3 and Y 4 At least one of X is a monovalent group represented by any one of the following formulas (Y-3) to (Y-5). 3 and X 4 are each independently a hydroxyl group, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. a3 and a4 are each independently an integer of 1 to 3. b3 and b4 are each independently an integer of 0 to 3, provided that 1≦a3+b3≦5 and 1≦a4+b4≦5 are satisfied. Z 2 is an organic group having a valence of (e+f). e and f are each independently an integer of 1 to 3. Y 3 , Y 4 , X 3 and X 4 When the same symbol is present multiple times in the formula, the groups having the same symbol are the same or different from each other. [ka] (In formulas (Y-3) to (Y-5), R a and R bare each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. "*" indicates a bond.) Effect of the Invention

[0011] According to the liquid crystal aligning agent of the present invention, since it contains the compound [A] together with the polymer component, it is possible to form a liquid crystal alignment film having excellent adhesion to the substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Liquid crystal alignment agent The liquid crystal aligning agent of the present disclosure contains a polymer component and at least one compound [A] selected from the group consisting of the compound represented by the above formula (1) and the compound represented by the above formula (2). Each component contained in the liquid crystal aligning agent and other components that are optionally blended as necessary will be described below.

[0013] In this specification, the term "hydrocarbon group" includes chain-like hydrocarbon groups, alicyclic hydrocarbon groups, and aromatic hydrocarbon groups. The term "chain-like hydrocarbon group" refers to a straight-chain hydrocarbon group and a branched hydrocarbon group that do not include a cyclic structure in the main chain and are composed only of a chain structure. However, they may be saturated or unsaturated. The term "alicyclic hydrocarbon group" refers to a hydrocarbon group that includes only an alicyclic hydrocarbon structure as a ring structure and does not include an aromatic ring structure. However, it does not have to be composed only of an alicyclic hydrocarbon structure, and it also includes those that have a chain structure as a part of it. The term "aromatic hydrocarbon group" refers to a hydrocarbon group that includes an aromatic ring structure as a ring structure. However, it does not have to be composed only of an aromatic ring structure, and it may include a chain structure or an alicyclic hydrocarbon structure as a part of it.

[0014] <Polymer component> The polymer component contained in the liquid crystal alignment agent may be crosslinked by the compound [A], and the main skeleton is not particularly limited. Examples of the polymer component include polyamic acid, polyamic acid ester, polyimide, polyamine, polyenamine, polyorganosiloxane, polyester, polyamide, polyamideimide, polystyrene, polybenzoxazole precursor, polybenzoxazole, cellulose derivative, polyacetal, polymaleimide, styrene-maleimide copolymer, or poly(meth)acrylate as the main skeleton and a polymer having a functional group that reacts (crosslinks) with the compound [A]. Note that (meth)acrylate means acrylate and methacrylate. Polyenamine is a polymer having a carbon-carbon double bond adjacent to the amino group of polyamine, and examples thereof include polyenaminoketone, polyenaminoester, polyenaminonitrile, and polyenaminosulfonyl.

[0015] As the polymer component, from the viewpoint of improving the liquid crystal alignment property and voltage retention property of the liquid crystal element, at least one selected from the group consisting of polyamic acid, polyamic acid ester, polyimide, polymer having a partial structure derived from a monomer having a polymerizable unsaturated bond, and polyorganosiloxane is preferable. Among these, from the viewpoint of improving the liquid crystal alignment property and voltage retention property and having a high degree of freedom in selecting the monomer, it is particularly preferable that the liquid crystal alignment agent of the present disclosure contains at least one polymer (hereinafter also referred to as "polymer (PA)") selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide as the polymer component.

[0016] In terms of being able to enhance the effect of improving the adhesion of the film by using the compound [A], the liquid crystal aligning agent of the present disclosure has a feature that at least a part of the polymer (PA) contained in the liquid crystal aligning agent is "* 4 -NR 11 R 12 ", "* 4 -NR 13 -* 5 ", "* 4 -NR 14 -CO-NR 15 -*5 ", "* 4 -NR 16 -CO-* 5 " and "* 4 -COOR 17 " (However, R 11 R is a hydrogen atom or a monovalent organic group. 12 is a protecting group. R 13 ~R 17 are each independently a hydrogen atom or a protecting group. 4 " and "* 5 " indicates a bond to a carbon atom constituting a carbon-carbon bond.) It is preferable that the polymer contains a structural unit derived from a diamine having at least one group (hereinafter also referred to as "specific group A") selected from the group consisting of: (a) a specific group A, (b) a specific group B, and (c) a specific group C. The use of such a polymer containing a structural unit having specific group A is preferable in that the reaction of the compound [A] with the polymer component can be promoted, and the adhesion between the liquid crystal alignment film and the substrate can be further increased.

[0017] In the specific group A, R 11 The monovalent organic group represented by the following formula is preferably a monovalent hydrocarbon group or protecting group having 1 to 10 carbon atoms. The protective group of the specific group A is preferably a monovalent organic group (thermally detachable group) that is detached by heat. Specific examples of the protective group of the amino group include, for example, a carbamate-based protective group, an amide-based protective group, an imide-based protective group, and a sulfonamide-based protective group. Among these, a carbamate-based protective group is preferable, and specific examples thereof include, for example, a tert-butoxycarbonyl group, a benzyloxycarbonyl group, a 1,1-dimethyl-2-haloethyloxycarbonyl group, a 1,1-dimethyl-2-cyanoethyloxycarbonyl group, a 9-fluorenylmethyloxycarbonyl group, an allyloxycarbonyl group, and a 2-(trimethylsilyl)ethoxycarbonyl group. Among these, a tert-butoxycarbonyl group (Boc group) is particularly preferable because of its high detachability by heat and the fact that the compound derived from the group detached by heating during film formation can be discharged outside the film as a gas. Carboxyl protecting group (R 17) include a tert-butyl group, an acetal ester structure of a carboxylic acid, a ketal ester structure of a carboxylic acid, and the like.

[0018] The specific group A may be introduced into either the main chain or the side chain of the polymer. 4 -NR 13 -* 5 " preferably constitutes a part of the main chain of the polymer. Here, the "main chain" of a polymer refers to the longest "trunk" part of the atomic chain of the polymer. The "side chain" refers to a part branched off from the "trunk" of the polymer.

[0019] Specific examples of the specific group A include the groups shown below. [ka] (In the formula, "*" indicates a bond to a carbon atom that constitutes a carbon-carbon bond.)

[0020] In the polymer (PA) containing a structural unit derived from a monomer having a specific group A, the content of the structural unit derived from the monomer having the specific group A is preferably 2 mol% or more, more preferably 5 mol% or more, and even more preferably 10 mol% or more, based on the total monomer units contained in the polymer. The content of the structural unit derived from the monomer having the specific group A is preferably 45 mol% or less, more preferably 40 mol% or less, and even more preferably 30 mol% or less, based on the total monomer units contained in the polymer. The specific group A contained in the polymer (PA) may be of only one type, or may be of two or more types.

[0021] The polymer component contained in the liquid crystal aligning agent of the present disclosure preferably has a group (hereinafter also referred to as "aligning group") capable of imparting a pretilt angle to liquid crystal molecules in a liquid crystal layer when a liquid crystal alignment film is disposed adjacent to the liquid crystal layer. The aligning group here refers to a group capable of imparting liquid crystal alignment ability to an organic film formed by the liquid crystal aligning agent without light irradiation. Specific examples of the aligning group include an alkyl group having 4 to 20 carbon atoms, an alkoxy group having 4 to 20 carbon atoms, a fluoroalkyl group having 4 to 20 carbon atoms, a fluoroalkoxy group having 4 to 20 carbon atoms, a group having a mesogen structure in which two or more rings (preferably at least one ring selected from the group consisting of a cyclohexane ring, a benzene ring, and a naphthalene ring) are bonded directly or via a divalent linking group (for example, an oxygen atom, -CO-, or -COO-), and a group having a steroid skeleton.

[0022] The polymer component preferably contains, as a polymer having an orienting group, a polymer having a partial structure represented by the following formula (3). *-L 1 -R 1 -R 2 -R 3 -R 4 …(3) (In formula (3), L 1 is a single bond, -O-, -CO-, -COO-* 1 , -OCO-* 1 , -NR 25 -, -NR 25 -CO-* 1 , -CO-NR 25 -* 1 an alkanediyl group having 1 to 6 carbon atoms, a divalent group in which a hydrogen atom of an alkanediyl group having 2 to 6 carbon atoms is substituted with a hydroxyl group, -OR 26 -* 1 , or -R 26 -O-* 1 (However, R 25 R is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. 26 is an alkanediyl group having 1 to 3 carbon atoms. 1 " is R 1 It indicates that it is a bond with . ) R 1 and R3 R is each independently a single bond, a substituted or unsubstituted phenylene group, or a substituted or unsubstituted cycloalkylene group. 2 represents a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted cycloalkylene group, or -R 27 -B 1 -R 28 -(However, R 27 and R 28 are each independently a substituted or unsubstituted phenylene group or cycloalkylene group. 1 is a single bond, -O-, -COO-* 2 , -OCO-* 2 , -OCH2-* 2 , -CH2O-* 2 or an alkanediyl group having 1 to 3 carbon atoms. 2 " is R 28 It indicates that it is a bond with . ) R 4 is a hydrogen atom, a fluorine atom, a cyano group, CH3COO-* 3 ("* 3 " is R 3 and R represents a bond to the alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a fluoroalkoxy group having 1 to 18 carbon atoms, a hydrocarbon group having 17 to 51 carbon atoms and a steroid skeleton, or a monovalent group in which a hydrogen atom of an alkyl group or a fluoroalkyl group having 1 to 18 carbon atoms is substituted with a cyano group. 1 , R 2 and R 3 are all single bonds, or R 1 , R 2 and R 3 When the total number of substituted or unsubstituted phenylene groups and cycloalkylene groups contained in R is 1, 4 is an alkyl group having 4 to 18 carbon atoms, a fluoroalkyl group having 4 to 18 carbon atoms, an alkoxy group having 4 to 18 carbon atoms, a fluoroalkoxy group having 4 to 18 carbon atoms, or a hydrocarbon group having a steroid skeleton and 17 to 51 carbon atoms. "*" indicates a bond.)

[0023] In the above formula (3), L 1 The alkanediyl group represented by the formula (I) is preferably linear. 25 Examples of the monovalent hydrocarbon group having 1 to 10 carbon atoms represented by the formula (I) include a chain hydrocarbon group, an alicyclic hydrocarbon group, and an aromatic hydrocarbon group, and preferably an alkyl group having 1 to 3 carbon atoms. R 4 With respect to R, it is preferable that the alkyl group having 1 to 18 carbon atoms, the fluoroalkyl group having 1 to 18 carbon atoms, the alkoxy group having 1 to 18 carbon atoms, the fluoroalkoxy group having 1 to 18 carbon atoms, or the monovalent group in which a hydrogen atom of an alkyl group or a fluoroalkyl group having 1 to 18 carbon atoms is substituted with a cyano group is linear. These groups preferably have 2 to 18 carbon atoms, more preferably 3 to 18 carbon atoms, and even more preferably 4 to 18 carbon atoms. 4 Examples of the hydrocarbon group having a steroid skeleton and 17 to 51 carbon atoms include a cholestanyl group, a cholesteryl group, and a lanostannyl group.

[0024] From the viewpoint of obtaining a liquid crystal element exhibiting good liquid crystal alignment, the alignment group is R 1 , R 2 and R 3 At least one of a substituted or unsubstituted phenylene group and a substituted or unsubstituted cycloalkylene group is selected from R 1 , R 2 and R 3 It is preferable that the total number of these is 2 or more, and more preferable that the total number of these is 2 to 4. Specific examples of the orienting group include groups represented by the following formulas (3-1) to (3-10). [ka] (In formulas (3-1) to (3-10), R 20 X is a fluorine atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, a fluoroalkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a fluoroalkoxy group having 1 to 20 carbon atoms. 21is -O-, -COO-, or an alkanediyl group having 1 to 3 carbon atoms. "*" indicates a bond.)

[0025] The liquid crystal aligning agent of the present disclosure preferably contains at least one polymer selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide as a polymer having an alignment group. In the polymer, the content of the structural unit having an alignment group is preferably 1 mol% or more, more preferably 3 mol% or more, and even more preferably 5 mol% or more, based on the total amount of the monomer units contained in the polymer. The content of the structural unit having an alignment group is preferably 40 mol% or less, more preferably 35 mol% or less, and even more preferably 30 mol% or less, based on the total amount of the monomer units contained in the polymer. The alignment group contained in the polymer component may be only one type, or may be two or more types.

[0026] Next, preferred examples of the polymer contained in the liquid crystal aligning agent of the present disclosure will be described.

[0027] (Polyamic acid) The polyamic acid can be obtained by reacting a tetracarboxylic dianhydride with a diamine compound.

[0028] Tetracarboxylic acid dianhydride Examples of the tetracarboxylic dianhydride used in the synthesis of the polyamic acid include aliphatic tetracarboxylic dianhydrides, alicyclic tetracarboxylic dianhydrides, aromatic tetracarboxylic dianhydrides, etc. Specific examples of these include aliphatic tetracarboxylic dianhydrides such as 1,2,3,4-butanetetracarboxylic dianhydride; Examples of alicyclic tetracarboxylic dianhydrides include 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 5-(2,5-dioxotetrahydrofuran-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8-methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 2,4,6,8-tetracarboxybis(tricarboxylic acid dianhydride), and the like. Examples of the aromatic tetracarboxylic dianhydride include pyromellitic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, ethylene glycol bisanhydrotrimate, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, and 4,4'-carbonyldiphthalic anhydride. In addition, the tetracarboxylic dianhydride described in JP-A-2010-97188 can be used. The tetracarboxylic dianhydride can be used alone or in combination of two or more.

[0029] The tetracarboxylic dianhydride used in the synthesis of the polyamic acid preferably contains at least one selected from the group consisting of an aliphatic tetracarboxylic dianhydride and an alicyclic tetracarboxylic dianhydride, and more preferably contains an alicyclic tetracarboxylic dianhydride, in that a liquid crystal alignment film exhibiting good voltage retention characteristics can be obtained. The amount of the alicyclic tetracarboxylic dianhydride used is preferably 20 mol % or more, more preferably 40 mol % or more, and even more preferably 50 mol % or more, based on the total amount of the tetracarboxylic dianhydride used in the synthesis of the polyamic acid.

[0030] Diamine compounds The diamine compound used in the synthesis of polyamic acid may be a known diamine compound. Examples of the diamine compound include aliphatic diamines, alicyclic diamines, aromatic diamines, diaminoorganosiloxanes, etc. The diamine compound used in the synthesis of polyamic acid preferably contains a diamine having a specific group A, because it has high reactivity with the compound [A] by heating and can further promote crosslinking.

[0031] Specific examples of the diamine having the specific group A include compounds represented by each of the following formulas (d-1-1) to (d-1-28). [ka] [ka] [ka] [ka] (In the formula, Boc represents a tert-butoxycarbonyl group.)

[0032] When synthesizing a polymer containing a structural unit derived from a monomer having a specific group A as the polymer (PA), the amount of the diamine having the specific group A is preferably 4 mol% or more, more preferably 10 mol% or more, and even more preferably 20 mol% or more, based on the total amount of diamines used in the synthesis of the polymer. The amount of the diamine having the specific group A is preferably 90 mol% or less, more preferably 80 mol% or less, and even more preferably 60 mol% or less, based on the total amount of diamines used in the synthesis of the polymer. When synthesizing the polymer (PA), the diamine having the specific group A may be used alone or in combination of two or more.

[0033] When forming a liquid crystal alignment film for a vertical alignment type or PSA type liquid crystal element, it is preferable to use a diamine having an alignment group together with a diamine having a specific group A in synthesizing the polymer (PA). The diamine having an alignment group is preferably a diamine having a partial structure represented by the above formula (3). Specific examples of diamines having an alignment group include dodecanoxy-2,4-diaminobenzene, pentadecanoxy-2,4-diaminobenzene, hexadecanoxy-2,4-diaminobenzene, octadecanoxy-2,4-diaminobenzene, pentadecanoxy-2,5-diaminobenzene, octadecanoxy-2,5-diaminobenzene, cholestanyloxy-3,5-diaminobenzene, cholestanyloxy-3,5-diaminobenzene, cholestanyloxy-2,4 ... Aminobenzene, cholestanyl 3,5-diaminobenzoate, cholestenyl 3,5-diaminobenzoate, lanostannyl 3,5-diaminobenzoate, 3,6-bis(4-aminobenzoyloxy)cholestane, 3,6-bis(4-aminophenoxy)cholestane, 4-(4'-trifluoromethoxybenzoyloxy)cyclohexyl-3,5-diaminobenzoate, 1,1-bis(4-((aminophenyl)methyl)phenyl)-4-butylcyclohexane, 3,5-diaminobenzoic acid = 5ξ-cholestan-3-yl, the following formula (E-1) [ka] (In formula (E-1), X I and X II are each independently a single bond, -O-, *-COO- or *-OCO- (where "*" represents X I ) and R I is an alkanediyl group having 1 to 3 carbon atoms, and R II is a single bond or an alkanediyl group having 1 to 3 carbon atoms, a is 0 or 1, b is an integer of 0 to 2, c is an integer of 1 to 20, and d is 0 or 1. However, a and b cannot be 0 at the same time. Examples of the compound include compounds represented by the following formula:

[0034] When synthesizing a polymer having an orientation group as the polymer (PA), the amount of diamine having an orientation group used is preferably 2 mol% or more, more preferably 6 mol% or more, and even more preferably 10 mol% or more, based on the total amount of diamine used in the synthesis of the polymer. The amount of diamine having an orientation group used is preferably 80 mol% or less, more preferably 70 mol% or less, and even more preferably 60 mol% or less, based on the total amount of diamine used in the synthesis of the polymer. When synthesizing the polymer (PA), one type of diamine having an orientation group may be used alone, or two or more types may be used in combination.

[0035] In addition to the above, the diamine compounds used in the synthesis of polyamic acid include aliphatic diamines such as metaxylylenediamine, 1,3-propanediamine, tetramethylenediamine, pentamethylenediamine, and hexamethylenediamine; alicyclic diamines such as 1,4-diaminocyclohexane and 4,4'-methylenebis(cyclohexylamine); Aromatic diamines include p-phenylenediamine, 4,4'-diaminodiphenylmethane, 4-aminophenyl-4-aminobenzoate, 4,4'-diaminoazobenzene, 1,5-bis(4-aminophenoxy)pentane, 1,2-bis(4-aminophenoxy)ethane, 1,6-bis(4-aminophenoxy)hexane, bis[2-(4-aminophenyl)ethyl]hexanedioic acid, 2,6-diaminopyridine, 1,4-bis-(4-aminophenyl)-piperazine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4,4'-diaminodiphenyl ether, and 2,2-bis[4-(4-aminophenoxy)phenyl]propionate. Examples of the diaminoorganosiloxane include 1,3-bis(3-aminopropyl)-tetramethyldisiloxane, 1,4-bis(4-aminophenyl)hexafluoropropane, 4,4'-(phenylenediisopropylidene)bisaniline, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-[4,4'-propane-1,3-diylbis(piperidine-1,4-diyl)]dianiline, 4,4'-diaminobenzanilide, 4,4'-diaminostilbene, and 1,4-bis(4-aminophenyl)-piperazine; and examples of the diaminoorganosiloxane include 1,3-bis(3-aminopropyl)-tetramethyldisiloxane; and the diamines described in JP-A-2010-97188 can also be used.

[0036] In the synthesis of the polyamic acid, the amount of the other diamine used is preferably 70 mol % or less, more preferably 60 mol % or less, and even more preferably 50 mol % or less, based on the total amount of the diamine used in the synthesis. In the synthesis of the polymer, the other diamine may be used alone or in combination of two or more kinds.

[0037] Synthesis of polyamic acid The polyamic acid can be obtained by reacting the above-mentioned tetracarboxylic dianhydride and diamine compound together with a molecular weight modifier as necessary. The ratio of the tetracarboxylic dianhydride and diamine compound used in the synthesis reaction of the polyamic acid is preferably such that the acid anhydride group of the tetracarboxylic dianhydride is 0.2 to 2 equivalents per equivalent of the amino group of the diamine compound. Examples of the molecular weight modifier include acid monoanhydrides such as maleic anhydride, phthalic anhydride, and itaconic anhydride, monoamine compounds such as aniline, cyclohexylamine, and n-butylamine, and monoisocyanate compounds such as phenyl isocyanate and naphthyl isocyanate. The ratio of the molecular weight modifier used is preferably 20 parts by mass or less per 100 parts by mass of the total of the tetracarboxylic dianhydride and diamine compound used.

[0038] The synthesis reaction of the polyamic acid is preferably carried out in an organic solvent, preferably at a reaction temperature of −20° C. to 150° C., and for a reaction time of 0.1 to 24 hours. Examples of the organic solvent used in the reaction include aprotic polar solvents, phenolic solvents, alcohols, ketones, esters, ethers, halogenated hydrocarbons, and hydrocarbons. Particularly preferred organic solvents are one or more selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethylsulfoxide, γ-butyrolactone, tetramethylurea, hexamethylphosphortriamide, m-cresol, xylenol, and halogenated phenols, or a mixture of one or more of these with other organic solvents (e.g., butyl cellosolve, diethylene glycol diethyl ether, etc.). The amount (a) of the organic solvent used is preferably an amount such that the total amount (b) of the tetracarboxylic dianhydride and the diamine is 0.1 to 50% by mass relative to the total amount (a+b) of the reaction solution. In this manner, a reaction solution in which polyamic acid is dissolved is obtained. This reaction solution may be used as it is for the preparation of a liquid crystal aligning agent, or the polyamic acid contained in the reaction solution may be isolated and then used for the preparation of a liquid crystal aligning agent.

[0039] (Polyamic acid ester) The polyamic acid ester can be obtained, for example, by a method of reacting the polyamic acid obtained by the above synthesis reaction with an esterifying agent, a method of reacting a tetracarboxylic acid diester with a diamine compound, or a method of reacting a tetracarboxylic acid diester dihalide with a diamine compound. The polyamic acid ester contained in the liquid crystal aligning agent may have only an amic acid ester structure, or may be a partially esterified product in which an amic acid structure and an amic acid ester structure coexist. The reaction solution in which the polyamic acid ester is dissolved may be used for preparing the liquid crystal aligning agent as it is, or the polyamic acid ester contained in the reaction solution may be isolated and then used for preparing the liquid crystal aligning agent.

[0040] (Polyimide) The polyimide can be obtained, for example, by dehydrating and cyclizing the polyamic acid synthesized as described above to imidize it. The polyimide may be a complete imidized product in which all amic acid structures of the polyamic acid precursor are dehydrated and cyclized, or a partial imidized product in which only a part of the amic acid structures are dehydrated and cyclized, and an amic acid structure and an imide ring structure coexist. The polyimide used in the reaction preferably has an imidization rate of 20 to 99%, more preferably 30 to 90%. This imidization rate is the ratio of the number of imide ring structures to the total number of amic acid structures and the number of imide ring structures of the polyimide, expressed as a percentage. Here, a part of the imide rings may be isoimide rings.

[0041] The dehydration ring-closing of polyamic acid is preferably carried out by dissolving polyamic acid in an organic solvent, adding a dehydrating agent and a dehydration ring-closing catalyst to the solution, and heating as necessary. In this method, the dehydrating agent may be, for example, an acid anhydride such as acetic anhydride, propionic anhydride, or trifluoroacetic anhydride. The amount of the dehydrating agent used is preferably 0.01 to 20 moles per mole of the amic acid structure of the polyamic acid. The dehydration ring-closing catalyst may be, for example, a tertiary amine such as pyridine, collidine, lutidine, or triethylamine. The amount of the dehydration ring-closing catalyst used is preferably 0.01 to 10 moles per mole of the dehydrating agent used. Examples of organic solvents used in the dehydration ring-closing reaction include the organic solvents exemplified as those used in the synthesis of polyamic acid. The reaction temperature of the dehydration ring-closing reaction is preferably 0 to 180° C. The reaction time is preferably 1.0 to 120 hours. The reaction solution containing the polyimide thus obtained may be used as it is for the preparation of a liquid crystal aligning agent, or the polyimide may be isolated and then used for the preparation of a liquid crystal aligning agent. The polyimide may also be obtained by imidizing a polyamic acid ester.

[0042] When a liquid crystal alignment ability is imparted to an organic film formed using a liquid crystal alignment agent by a photoalignment method, it is preferable that at least a part of the polymer component is a polymer having a photoalignment group. The photoalignment group refers to a functional group capable of imparting anisotropy to a film by a photoreaction such as a photoisomerization reaction, a photodimerization reaction, a photo-Fries rearrangement reaction, or a photodecomposition reaction caused by light irradiation.

[0043] Specific examples of the photo-alignment group include an azobenzene-containing group containing azobenzene or a derivative thereof as a basic skeleton, a cinnamic acid structure-containing group containing cinnamic acid or a derivative thereof (cinnamic acid structure) as a basic skeleton, a chalcone-containing group containing chalcone or a derivative thereof as a basic skeleton, a benzophenone-containing group containing benzophenone or a derivative thereof as a basic skeleton, a coumarin-containing group containing coumarin or a derivative thereof as a basic skeleton, a cyclobutane-containing structure containing cyclobutane or a derivative thereof as a basic skeleton, a stilbene-containing group having stilbene or a derivative thereof as a basic skeleton, a phenylbenzoate-containing group containing phenylbenzoate or a derivative thereof as a basic skeleton, etc. Among these, the photo-alignment group is preferably at least one selected from the group consisting of an azobenzene-containing group, a cinnamic acid structure-containing group, a chalcone-containing group, a stilbene-containing group, a cyclobutane-containing structure, and a phenylbenzoate-containing group, and it is preferable that the photo-alignment group is a cinnamic acid structure-containing group or a cyclobutane-containing structure in terms of high sensitivity to light and ease of introduction into a polymer.

[0044] The polymer having a photo-alignable group can be obtained, for example, by (1) a method of obtaining by polymerization using a monomer having a photo-alignable group, or (2) a method of synthesizing a polymer having an epoxy group in a side chain, and reacting the epoxy group-containing polymer obtained by the synthesis with a carboxylic acid having a photo-alignable group. The content ratio of the photo-alignable group in the polymer can be appropriately set according to the type of the photo-alignable group so as to impart a desired liquid crystal alignment ability to the coating film. For example, in the case of a cinnamic acid structure-containing group, the content ratio of the photo-alignable group is preferably 5 mol % or more, more preferably 10 to 60 mol %, based on the total structural units of the polymer having a photo-alignable group. In the case of a cyclobutane-containing structure, the content ratio of the photo-alignable group is preferably 50 mol % or more, more preferably 80 mol % or more, based on the total structural units of the polymer having a photo-alignable group. Note that, as the polymer having a photo-alignable group, one type may be used alone, or two or more types may be used in combination.

[0045] The polymer component contained in the liquid crystal alignment agent may be one type alone or multiple types. For example, a first polymer and a second polymer having a higher polarity than the first polymer are contained in the liquid crystal alignment agent. In this case, the second polymer having a higher polarity is unevenly distributed in the lower layer, and the first polymer is unevenly distributed in the upper layer, which is preferable in that phase separation can occur. Preferable embodiments of the polymer component of the liquid crystal alignment agent include the following (I) to (III). (I) An embodiment in which the first polymer and the second polymer are polymers selected from the group consisting of polyamic acids, polyamic acid esters, and polyimides. (II) An embodiment in which one of the first polymer and the second polymer is a polymer selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide, and the other is polyorganosiloxane. (III) An embodiment in which one of the first polymer and the second polymer is at least one polymer selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide, and the other is a polymer having a structural unit derived from a monomer having a polymerizable unsaturated bond (hereinafter also referred to as "polymer (Pm)").

[0046] (Polyorganosiloxane) The polyorganosiloxane contained in the liquid crystal alignment agent can be obtained, for example, by hydrolysis and condensation of a hydrolyzable silane compound. Examples of the hydrolyzable silane compound include alkoxysilane compounds such as tetramethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, and dimethyldiethoxysilane; nitrogen- and sulfur-containing alkoxysilane compounds such as 3-mercaptopropyltriethoxysilane, mercaptomethyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N-(3-cyclohexylamino)propyltrimethoxysilane; 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-glycidoxypropyltrimethoxysilane; Examples of the epoxy group-containing silane compounds include ethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane; unsaturated bond-containing alkoxysilane compounds include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltriethoxysilane, and p-styryltrimethoxysilane; and trimethoxysilylpropylsuccinic anhydride. The hydrolyzable silane compounds may be used alone or in combination of two or more of these. The term "(meth)acryloxy" includes "acryloxy" and "methacryloxy".

[0047] The above hydrolysis and condensation reaction is carried out by reacting one or more of the above silane compounds with water, preferably in the presence of a suitable catalyst and an organic solvent. In the reaction, the proportion of water used is preferably 1 to 30 moles per mole of the silane compounds (total amount). Examples of the catalyst used include acids, alkali metal compounds, organic bases, titanium compounds, and zirconium compounds. The amount of the catalyst used varies depending on the type of catalyst, reaction conditions such as temperature, and should be set appropriately, but is preferably 0.01 to 3 moles per the total amount of the silane compounds. Examples of the organic solvent used include hydrocarbons, ketones, esters, ethers, and alcohols, and among these, it is preferable to use a water-insoluble or poorly water-soluble organic solvent. The proportion of the organic solvent used is preferably 10 to 10,000 parts by mass per 100 parts by mass of the total silane compounds used in the reaction.

[0048] The above hydrolysis and condensation reaction is preferably carried out by heating, for example, in an oil bath. In this case, the heating temperature is preferably 130°C or less, and the heating time is preferably 0.5 to 12 hours. After the reaction is completed, the organic solvent layer separated from the reaction solution is dried with a desiccant as necessary, and then the solvent is removed to obtain the desired polyorganosiloxane. The method for synthesizing polyorganosiloxane is not limited to the above hydrolysis and condensation reaction, and may be, for example, a method in which a hydrolyzable silane compound is reacted in the presence of oxalic acid and alcohol.

[0049] When polyorganosiloxane is made into a polymer having a functional group such as an orientation group or a photo-orientation group, the synthesis method is not particularly limited. For example, a method of synthesizing a polyorganosiloxane having an epoxy group in a side chain (hereinafter also referred to as "epoxy group-containing polyorganosiloxane") using an epoxy group-containing silane compound as at least a part of the raw material, and then reacting the epoxy group-containing polyorganosiloxane with a carboxylic acid having a functional group, etc. can be mentioned. This method is simple and preferable in that it can increase the introduction rate of the functional group. In addition, a polyorganosiloxane having a functional group in a side chain may be synthesized by a reaction containing a hydrolyzable silane compound having a functional group in a monomer. The weight average molecular weight (Mw) of the polyorganosiloxane in terms of polystyrene measured by GPC is preferably in the range of 100 to 50,000, more preferably in the range of 200 to 10,000.

[0050] (Polymer (Pm)) Examples of monomers having a polymerizable unsaturated bond used in the synthesis of the polymer (Pm) include compounds having a (meth)acryloyl group, a vinyl group, a vinylphenyl group, a maleimide group, etc. As the polymer (Pm), at least one selected from the group consisting of poly(meth)acrylates, maleimide polymers, and styrene-maleimide copolymers can be preferably used in terms of ease of introduction of functional groups and good liquid crystal alignment properties.

[0051] Specific examples of monomers having a polymerizable unsaturated bond include unsaturated carboxylic acids such as (meth)acrylic acid, α-ethylacrylic acid, maleic acid, fumaric acid, and vinylbenzoic acid; unsaturated carboxylic acid esters such as alkyl (meth)acrylates (e.g., methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc.), cycloalkyl (meth)acrylates, benzyl (meth)acrylate, trimethoxysilylpropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxybutyl (meth)acrylate, and 4-hydroxybutyl glycidyl ether acrylate; unsaturated polyvalent carboxylic acid anhydrides such as maleic anhydride; and (meth)acrylic compounds such as: Aromatic vinyl compounds such as styrene, methylstyrene, divinylbenzene, and 4-(glycidyloxymethyl)styrene; conjugated diene compounds such as 1,3-butadiene and 2-methyl-1,3-butadiene; Examples of the maleimide compounds include N-methylmaleimide, N-cyclohexylmaleimide, N-phenylmaleimide, 4-(2,5-dioxo-3-pyrrolin-1-yl)benzoic acid, N-(4-glycidyloxyphenyl)maleimide, N-glycidylmaleimide, 3-maleimide benzoic acid, 3-maleimide propionic acid, 3-(2,5-dioxo-3-pyrrolin-1-yl)benzoic acid, and methyl 4-(2,5-dioxo-3-pyrrolin-1-yl)benzoate. In addition, when the polymer (Pm) is a polymer having a functional group, a compound having a functional group can also be used as a monomer having a polymerizable unsaturated bond. The monomer having a polymerizable unsaturated bond can be used alone or in combination of two or more.

[0052] The polymer (Pm) can be obtained, for example, by polymerizing a monomer having a polymerizable unsaturated bond in the presence of a polymerization initiator. As the polymerization initiator to be used, for example, an azo compound such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), or 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) is preferable. The proportion of the polymerization initiator to be used is preferably 0.01 to 30 parts by mass with respect to 100 parts by mass of the total monomers to be used in the reaction. The polymerization reaction is preferably carried out in an organic solvent. As the organic solvent to be used in the reaction, for example, alcohol, ether, ketone, amide, ester, and hydrocarbon compound can be mentioned, and diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether acetate, and the like are preferable. The reaction temperature is preferably 30°C to 120°C, and the reaction time is preferably 1 to 36 hours. The amount of the organic solvent (a) used is preferably such that the total amount (b) of the monomers used in the reaction is 0.1 to 60% by mass relative to the total amount (a+b) of the reaction solution. The weight average molecular weight (Mw) of the polymer (Pm) measured by GPC in terms of polystyrene is preferably 250 to 500,000, more preferably 500 to 100,000.

[0053] In the above embodiments (II) and (III), the total content of the polyamic acid, polyamic acid ester and polyimide is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 50 to 98% by mass, based on the total amount of polymer components contained in the liquid crystal alignment agent, from the viewpoint of obtaining a liquid crystal element having sufficiently high liquid crystal alignment properties and voltage retention properties. When liquid crystal alignment ability is imparted to an organic film formed using a liquid crystal alignment agent by a photoalignment method, it is preferable to use at least one selected from the group consisting of polyorganosiloxane, poly(meth)acrylate and styrene-maleimide copolymer as a polymer having a photoalignment group, in that an alignment film having better liquid crystal alignment properties can be obtained.

[0054] From the viewpoint of sufficiently increasing the film strength, the content ratio of the polymer component in the liquid crystal alignment agent is preferably 50 mass % or more, more preferably 60 mass % or more, and even more preferably 70 mass % or more, relative to the total mass of the solid contents contained in the liquid crystal alignment agent (the total mass of the components other than the solvent of the liquid crystal alignment agent).

[0055] <Compound [A]> The compound [A] is at least one selected from the group consisting of compounds represented by the following formula (1) and compounds represented by the following formula (2). [ka] (In formula (1), Y 1 and Y 2 are each independently a hydrogen atom or a monovalent organic group. 1 and X 2 are each independently a hydroxyl group, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. a1 and a2 are each independently an integer of 1 to 3. b1 and b2 are each independently an integer of 0 to 3, provided that 1≦a1+b1≦5 and 1≦a2+b2≦5 are satisfied. Z 1 is a (c+d)-valent organic group that satisfies the following (i), (ii), or (iii): (i) a (c+d)-valent group having 1 to 8 carbon atoms in which at least one methylene group of a saturated chain hydrocarbon group is replaced with -O-, a (c+d)-valent group having 1 to 8 carbon atoms in which at least one hydrogen atom of a saturated chain hydrocarbon group is replaced with a fluorine atom and at least one methylene group of the saturated chain hydrocarbon group is replaced with -O-, or a (c+d)-valent group having 2 to 8 carbon atoms in which at least one hydrogen atom of a saturated chain hydrocarbon group is replaced with a carboxyl group. (ii) A (c+d)-valent saturated hydrocarbon group having 11 or more carbon atoms, or a (c+d)-valent aromatic hydrocarbon group having 7 or more carbon atoms. (iii) -S-, -SO2- or -CO-. c and d are each independently an integer of 1 to 3. However, in the case of (iii) above, c+d=2. Y 1 , Y2 , X 1 and X 2 When the same symbol is present multiple times in the formula, the groups having the same symbol are the same or different from each other. [ka] (In formula (2), Y 3 and Y 4 are each independently a hydrogen atom or a monovalent organic group. 3 and Y 4 At least one of X is a monovalent group represented by any one of the following formulas (Y-1) to (Y-6). 3 and X 4 are each independently a hydroxyl group, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. a3 and a4 are each independently an integer of 1 to 3. b3 and b4 are each independently an integer of 0 to 3, provided that 1≦a3+b3≦5 and 1≦a4+b4≦5 are satisfied. Z 2 is an organic group having a valence of (e+f). e and f are each independently an integer of 1 to 3. Y 3 , Y 4 , X 3 and X 4 When the same symbol is present multiple times in the formula, the groups having the same symbol are the same or different from each other. [ka] (In formulas (Y-1) to (Y-6), R a and R b are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. "*" indicates a bond.)

[0056] (Compound represented by the above formula (1)) In the above formula (1), Y 1 and Y 2 The monovalent organic group represented by the formula (I) is a monovalent hydrocarbon group having 1 to 20 carbon atoms, at least one of the methylene groups of the hydrocarbon group being -O-, -S-, -CO-, -COO-, -NR b -,-CONRb - or the like. b represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms, a monovalent heterocyclic group, etc. 1 , Y 2 When is a monovalent hydrocarbon group, the monovalent hydrocarbon group is preferably an alkyl group having 1 to 7 carbon atoms, a cycloalkyl group having 4 to 10 carbon atoms, or an aryl group having 6 to 12 carbon atoms, more preferably an alkyl group having 1 to 7 carbon atoms.

[0057] Y 1 and Y 2 The monovalent organic group represented by the formula Y is preferably a group which is eliminated by heating during film formation. 1 and Y 2 When is a group that is eliminated by heat, preferred specific examples thereof include ether-based protecting groups such as an alkyl group having 1 to 7 carbon atoms, a benzyl group, and a p-methoxybenzyl group; acetal-based protecting groups such as a methoxymethyl group, an ethoxyethyl group, and a 2-tetrahydropyranyl group; acyl-based protecting groups such as an acetyl group and a benzoyl group; allyl-based protecting groups such as an allyl group and a methallyl group; and silyl ether-based protecting groups such as a trimethylsilyl group, a triethylsilyl group, and a tert-butyldimethylsilyl group. From the viewpoint of achieving both ease of elimination by heat and storage stability, among these, an ether-based protecting group, an acetal-based protecting group, or an acetyl group is preferred, and an alkyl group having 1 to 7 carbon atoms, a 2-tetrahydropyranyl group, a methoxymethyl group, a 1-ethoxyethyl group, or an acetyl group is more preferred.

[0058] Y 1 and Y 2 From the viewpoint of increasing the adhesion between the liquid crystal alignment film and the substrate and the storage stability of the liquid crystal alignment agent, among the above, a hydrogen atom, an ether-based protecting group, an acetal-based protecting group, or an acetyl group is preferred, and a hydrogen atom, an alkyl group having 1 to 7 carbon atoms, an acetyl group, a 2-tetrahydropyranyl group, a methoxymethyl group, or a 1-ethoxyethyl group is more preferred.

[0059] X 1 and X 2is preferably a hydroxyl group, an alkyl group having 1 to 3 carbon atoms, or an alkoxy group having 1 to 3 carbon atoms. From the viewpoint of obtaining a sufficient effect of improving the adhesion between the liquid crystal alignment film and the substrate, a1 and a2 are each preferably 2 or 3. a1+b1 and a2+b2 are each preferably 2 or more, and more preferably 2 to 4. With regard to c and d, from the viewpoint of obtaining a sufficient effect of improving adhesion to a substrate and from the viewpoint of a balance between storage stability, c+d is preferably 2 to 6, and more preferably 2 to 4.

[0060] Z 1 If satisfies (i), then Z 1 is the following (Z1), (Z2), or (Z3). (Z1) A (c+d)-valent group having 1 to 8 carbon atoms in which at least one methylene group of a saturated chain hydrocarbon group is replaced with -O-. (Z2) A (c+d)-valent group having 1 to 8 carbon atoms in which at least one hydrogen atom of a saturated chain hydrocarbon group is replaced with a fluorine atom and at least one methylene group of the saturated chain hydrocarbon group is replaced with -O-. (Z3) A (c+d)-valent group having 2 to 8 carbon atoms in which at least one hydrogen atom of a saturated chain hydrocarbon group is substituted with a carboxyl group.

[0061] In the above group (Z1), the saturated chain hydrocarbon group may be linear or branched. When the saturated chain hydrocarbon group is linear, it is preferable because it can increase the adhesion between the alignment film and the substrate (hereinafter also referred to as "narrow width adhesion") even when the width of the sealant (sealing width) is narrowed when bonding a pair of substrates together via the sealant after the formation of the liquid crystal alignment film. When the saturated chain hydrocarbon group is linear, c+d is preferably 2.

[0062] In the group (Z1), the position of the oxygen atom in the saturated chain hydrocarbon group is not particularly limited. The oxygen atom may be present between the carbon-carbon bonds of the saturated chain hydrocarbon group, at the end of the saturated chain hydrocarbon group (i.e., the part bonded to the benzene ring in formula (1)), or both between the carbon-carbon bonds and at the end. Among these, the group (Z1) is a group represented by the formula (1) represented by the formula (1) represented by the formula (1). 1 and Z is preferably a group bonded via an oxygen atom to at least one benzene ring connected via 1 It is more preferable that the benzene ring is a group bonded via an oxygen atom to all of the benzene rings connected via the abovementioned oxygen atom. The number of oxygen atoms in the group (Z1) is preferably 2 or more, and more preferably 2 to 6, in terms of improving narrow width adhesion.

[0063] The group (Z2) is a group in which at least one hydrogen atom bonded to a carbon atom in the group (Z1) is replaced with a fluorine atom. In the group (Z2), the saturated chain hydrocarbon group is preferably linear for the same reasons as in the group (Z1). For specific examples and preferred examples of the position of the oxygen atom in the group (Z2), the explanation of the group (Z1) is incorporated herein.

[0064] In the above group (Z3), the saturated chain hydrocarbon group may be linear or branched. The position and number of the carboxyl group in the saturated chain hydrocarbon group are not particularly limited. In order to obtain a liquid crystal alignment film with higher narrow-width adhesion, it is preferable that the carboxyl group is bonded to the saturated chain hydrocarbon portion connecting two or more benzene rings in formula (1) via an alkanediyl group. In this case, the degree of freedom of movement of the carboxyl group is increased, which is preferable in that the self-crosslinking property can be increased. The number of carboxyl groups in the group (Z3) is preferably 1 to 6, and more preferably 1 to 3, from the viewpoint of achieving both narrow width adhesion and storage stability.

[0065] Z 1When satisfies (i), preferred specific examples of the compound represented by the above formula (1) include a compound represented by the following formula (1-z-1) and a compound represented by the following formula (1-z-2). [ka] (In formula (1-z-1), R 5 Y is an alkanediyl group having 1 to 8 carbon atoms, a fluoroalkanediyl group having 1 to 8 carbon atoms, or a divalent group having 2 to 8 carbon atoms containing -O- between the carbon-carbon bonds of the alkanediyl group. 1 , Y 2 , X 1 , X 2 , a1, a2, b1 and b2 are the same as defined in formula (1). [ka] (In formula (1-z-2), R 8 R is a single bond or a (c+1)-valent saturated chain hydrocarbon group. 9 R is a single bond or a (d+1)-valent saturated chain hydrocarbon group. 10 R is a (g+2)-valent saturated chain hydrocarbon group. 11 is an alkanediyl group, where R 8 , R 9 , R 10 and R 11 The total number of carbon atoms in is 2 to 8. g is an integer of 1 to 3. 1 , Y 2 , X 1 , X 2 , a1, a2, b1, b2, c and d are the same as those in formula (1).

[0066] In the above formula (1-z-1), R 5 is preferably "*-O-(CH2) h -O-*", "*-O-(CF2) h -O-*" or "*-O-(R 6 -O) i -*" (where R 6 is an alkanediyl group having 2 to 4 carbon atoms. h is an integer of 1 to 8. i is an integer of 1 to 4. In the above formula (1-z-2), c and d are each preferably 1 or 2, and more preferably 1, from the viewpoint of achieving a good balance between adhesion to a substrate and storage stability. g is preferably 1 or 2.

[0067] Z in the above formula (1) 1 By incorporating a compound satisfying (i) in the liquid crystal alignment agent, a liquid crystal alignment film having good adhesion to the substrate can be formed. In particular, it is preferable that a liquid crystal alignment film having excellent adhesion between the alignment film and the substrate (i.e., narrow width adhesion) can be formed even when the seal width is narrowed to narrow the frame of the liquid crystal element for the purpose of ensuring as wide an area of ​​movement as possible in a touch panel type liquid crystal element or for the purpose of miniaturizing the display panel. That is, Z in the above formula (1) 1 A compound that satisfies (i) can provide a liquid crystal alignment film that is excellent in adhesion to the substrate and is suitable for narrowing the frame of a liquid crystal element. In addition, by using the compound as a crosslinking agent, a liquid crystal element that exhibits a high voltage holding ratio can be obtained even when a liquid crystal alignment agent containing a crosslinking agent is used. 1 Among the groups (Z1) to (Z3), the group (Z1) or the group (Z3) is preferable since it has high compatibility with the polymer component and can improve the coatability and liquid crystal alignment properties.

[0068] Z 1 If (ii) is satisfied, then Z 1 is (Z4) or (Z5) below. (Z4) A (c+d)-valent saturated hydrocarbon group having 11 or more carbon atoms. (Z5) A (c+d)-valent aromatic hydrocarbon group having 7 or more carbon atoms.

[0069] Z 1 When is a group (Z4), Z 1 (i.e., the saturated hydrocarbon group) preferably has an alicyclic structure. In this case, a preferred specific example of the compound represented by the above formula (1) is a compound represented by the following formula (1-z-3). [ka] (In formula (1-z-3), R 12 R is a (c+1)-valent saturated chain hydrocarbon group or alicyclic group. 13 R is a (d+1)-valent saturated chain hydrocarbon group or alicyclic group. 14 and R 15 R is each independently a single bond or an alkanediyl group. 16 is a divalent group having an alkanediyl group or an alicyclic structure, provided that R 12 , R 13 , R 14 , R 15 and R 16 The total number of carbon atoms in R is 11 or more. 12 , R 13 and R 16 At least one of Y has an alicyclic structure. 1 , Y 2 , X 1 , X 2 , a1, a2, b1, b2, c and d are the same as those in formula (1).

[0070] In the above formula (1-z-3), R 12 and R 13 The alicyclic group represented by the formula (1) is a group in which (c+1) or (d+1) hydrogen atoms have been removed from the ring portion of an alicyclic hydrocarbon ring. The alicyclic hydrocarbon ring preferably has 4 or more ring members, more preferably 5 or more ring members, and even more preferably 5 to 12 ring members, in order to form a liquid crystal alignment film having high resistance to high temperature and humidity. From the viewpoint of easy availability of the compound, adhesion to the substrate, and achieving a good balance between high temperature and high humidity resistance, the alicyclic structure of the group (Z4) is particularly preferably a cyclopentane ring, a cyclohexane ring, or a cycloheptane ring. R 12 and R 13 From the viewpoint of improving the effect of high-temperature and high-humidity resistance, it is preferable that at least one of them is an alicyclic group, and it is more preferable that both of them are alicyclic groups.

[0071] R 14 and R 15 The alkanediyl group represented by the formula (I) may be linear or branched. 14and R 15 is preferably a single bond or an alkanediyl group having 1 to 5 carbon atoms, and more preferably a single bond or an alkanediyl group having 1 to 3 carbon atoms.

[0072] R 16 The alkanediyl group represented by the formula (I) may be linear or branched. 16 When R is an alkanediyl group, it preferably has 1 to 10 carbon atoms, and more preferably has 1 to 5 carbon atoms. 12 and R 13 When at least one of R is an alicyclic group, 16 is preferably an alkanediyl group. 16 When R is a divalent group having an alicyclic structure, 16 Examples of the group include a group represented by the following formula (r-1). [ka] (In formula (r-1), R 17 is an alkanediyl group. 18 R is a single bond or an alkanediyl group. 19 is a monovalent alicyclic group. "*" indicates a bond.)

[0073] In formula (r-1), R 17 R preferably has 1 to 3 carbon atoms. 18 is preferably a single bond or an alkanediyl group having 1 to 3 carbon atoms. 19 is preferably a substituted or unsubstituted cyclohexylene group. Examples of the substituent include a methyl group, an ethyl group, a fluorine atom, and the like. In terms of improving resistance to high temperature and humidity, each of c and d is preferably 2 or 3, and more preferably 2. R 12 , R 13 , R 14 , R 15 and R 16 From the viewpoints of improving the coatability and suppressing uneven alignment, the total number of carbon atoms is preferably 40 or less, and more preferably 30 or less.

[0074] Z1 When is a group (Z5), Z 1 Examples of the aromatic ring contained in the aromatic hydrocarbon group include a benzene ring, a naphthalene ring, an anthracene ring, and a fluorene ring. 1 When is a group (Z5), a preferred specific example of the compound represented by the above formula (1) includes a compound represented by the following formula (1-z-4). [ka] (In formula (1-z-4), R 20 R is a single bond or a (c+1)-valent saturated chain hydrocarbon group. 21 R is a single bond or a (d+1)-valent saturated chain hydrocarbon group. 22 is a divalent group having an aromatic ring structure. 20 , R 21 and R 22 The total number of carbon atoms in Y is 7 or more. 1 , Y 2 , X 1 , X 2 , a1, a2, b1, b2, c and d are the same as those in formula (1). 20 If is a single bond, c is 1. 21 If is a single bond, d is 1.)

[0075] In the above formula (1-z-4), R 22 is preferably a group represented by the following formula (r-2-1) or a group represented by the following formula (r-2-2). [ka] (In formula (r-2-1), R 23 is an alkanediyl group. 24 R is a single bond or an alkanediyl group. 25 In formula (r-2-2), R b is a substituent. t is an integer of 0 to 4. "*" indicates a bond.

[0076] In formula (r-2-1), R 23R may be linear or branched. 23 The carbon number of R is preferably 1 to 3. 24 is preferably a single bond or an alkanediyl group having 1 to 3 carbon atoms. 25 is preferably a substituted or unsubstituted phenyl group or naphthyl group, and examples of the substituent include a methyl group, an ethyl group, a fluorine atom, and the like.

[0077] In formula (r-2-2), R b Examples of the substituent represented by the formula (1) include a halogen atom, an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, an acetyl group, etc. t is preferably 0 to 2.

[0078] Each of c and d is preferably 1 or 2, and more preferably 1. R 20 , R 21 and R 22 From the viewpoints of improving the coatability and suppressing uneven alignment, the total number of carbon atoms is preferably 40 or less, and more preferably 30 or less.

[0079] Z in the above formula (1) 1 By incorporating a compound that satisfies (ii) into the liquid crystal alignment agent, a liquid crystal alignment film having good adhesion to the substrate can be formed. 1 The above structure is highly hydrophobic, and by incorporating such a compound [A] into a liquid crystal alignment agent, the performance is unlikely to deteriorate even when exposed to a high-temperature and high-humidity environment, and a liquid crystal alignment film having excellent resistance to high temperatures and high humidity can be formed. 1 According to the compound satisfying (ii), a liquid crystal alignment film having excellent adhesion to a substrate and high temperature and high humidity resistance can be obtained. In addition, by using the compound as a crosslinking agent, even when a liquid crystal alignment agent containing a crosslinking agent is used, it is preferable that a liquid crystal element having a high voltage holding ratio can be obtained.

[0080] Z 1 If satisfies (iii), then Z 1is -S-, -SO2- or -CO-. In this case, the compound represented by the above formula (1) can be represented by the following formula (1-z-5). [ka] (In formula (1-z-5), Z 3 is -S-, -SO2- or -CO-. 1 , Y 2 , X 1 , X 2 , a1, a2, b1 and b2 are the same as defined in formula (1).

[0081] Z in formula (1-z-5) 3 is preferably -S- or -SO2-, and more preferably -SO2-, in that a liquid crystal alignment film having excellent adhesion to the substrate can be formed even when the temperature during film formation is high (for example, 200° C. or higher).

[0082] Z in the above formula (1) 1 By incorporating a compound that satisfies (iii) into the liquid crystal aligning agent, a liquid crystal alignment film having good adhesion to the substrate can be formed. 1 By incorporating a compound [A] having a structure showing an electron-withdrawing group into the liquid crystal alignment agent, the liquid crystal alignment film is unlikely to peel off from the substrate even when the temperature during film formation (post-baking temperature) is high, and a liquid crystal alignment film having excellent adhesion to the substrate can be formed, which is advantageous. It is possible to shorten the film formation process by increasing the post-baking temperature in the manufacturing process, but 1 The compound satisfying (iii) is preferable in that the film is unlikely to peel off even if the post-baking temperature is increased, the process compatibility range is wide, and the decrease in the manufacturing yield can be suppressed. In addition, by using the compound as a crosslinking agent, it is preferable that a liquid crystal element exhibiting a high voltage holding ratio can be obtained even when the liquid crystal alignment agent contains a crosslinking agent.

[0083] Specific examples of the compound represented by the above formula (1) include Z 1As compounds satisfying (i), compounds represented by the following formulas (1-1-1) to (1-1-13) are mentioned; 1 As compounds satisfying (ii), compounds represented by the following formulas (1-2-1) to (1-2-12) are mentioned; 1 Examples of the compound satisfying (iii) include compounds represented by the following formulas (1-3-1) to (1-3-9). As the compound represented by the above formula (1), one type may be used alone, or two or more types may be used in combination. [ka] [ka] [ka] [ka] [ka]

[0084] (Compound represented by the above formula (2)) In the above formula (2), Y 3 and Y 4 The monovalent organic group represented by the formula (I) is a monovalent hydrocarbon group having 1 to 20 carbon atoms, at least one of the methylene groups of the hydrocarbon group being -O-, -S-, -CO-, -COO-, -NR b -,-CONR b - or the like. b represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms, a monovalent heterocyclic group, etc. 3 , Y 4When is a monovalent hydrocarbon group, the monovalent hydrocarbon group is preferably an alkyl group having 1 to 7 carbon atoms, a cycloalkyl group having 4 to 10 carbon atoms, or an aryl group having 6 to 12 carbon atoms, more preferably an alkyl group having 4 to 7 carbon atoms, a cycloalkyl group having 4 to 10 carbon atoms, or an aryl group having 6 to 12 carbon atoms, and even more preferably an alkyl group having 4 to 7 carbon atoms.

[0085] Y 3 and Y 4 The monovalent organic group represented by the formula Y is preferably a group which is eliminated by heating during film formation. 3 and Y 4 When Y is a group that is eliminated by heat, preferred specific examples include ether-based protecting groups such as an alkyl group having 1 to 7 carbon atoms, a benzyl group, and a p-methoxybenzyl group; acetal-based protecting groups such as a methoxymethyl group, an ethoxyethyl group, and a 2-tetrahydropyranyl group; acyl-based protecting groups such as an acetyl group and a benzoyl group; allyl-based protecting groups such as an allyl group and a methallyl group; and silyl ether-based protecting groups such as a trimethylsilyl group, a triethylsilyl group, and a tert-butyldimethylsilyl group. 3 and Y 4 A (meth)acryloyl group may be introduced into the compound represented by the above formula (2) as the monovalent organic group represented by the following formula: From the viewpoint of ease of elimination by heat, among these, an ether-based protecting group, an acetal-based protecting group, or an acetyl group is preferred, and an alkyl group having 1 to 7 carbon atoms, a 2-tetrahydropyranyl group, a methoxymethyl group, a 1-ethoxyethyl group, or an acetyl group is more preferred.

[0086] In the compound represented by the above formula (2), Y 3 and Y 4At least one of the groups is a group represented by any one of the above formulae (Y-1) to (Y-6). By incorporating such a compound into the liquid crystal alignment agent, it is preferable that the liquid crystal alignment film can be easily peeled off from the substrate (reworkability can be improved) when the liquid crystal alignment film is peeled off from the substrate and the substrate is reused (reworked) in the manufacturing process of the liquid crystal element, while increasing the adhesion of the liquid crystal alignment film to the substrate. In addition, by using the compound represented by the above formula (2) as a crosslinking agent, it is preferable that a liquid crystal element exhibiting a high voltage holding ratio can be obtained even when the liquid crystal alignment agent contains a crosslinking agent. From the viewpoint of achieving both the adhesion of the liquid crystal alignment film to the substrate and the reworkability, 3 and Y 4 Among the above formulas (Y-1) to (Y-6), a group represented by any one of the above formulas (Y-2) to (Y-6) is preferable, and furthermore, a group represented by any one of the above formulas (Y-2) and (Y-4) to (Y-6) is more preferable in terms of obtaining a liquid crystal element having excellent liquid crystal alignment properties and voltage holding ratio, and an alkyl group having 4 to 7 carbon atoms, a 2-tetrahydropyranyl group, a methoxymethyl group, a 1-ethoxyethyl group or an acetyl group is particularly preferable.

[0087] Y in the above formula (2) 3 and Y 4 Among these, the total number of groups represented by any one of the above formulae (Y-1) to (Y-6) is preferably 2 or more from the viewpoint of obtaining a liquid crystal alignment film having good adhesion to the substrate. From the viewpoint of obtaining a liquid crystal alignment film having a good balance between adhesion to the substrate and reworkability, the total number of groups represented by any one of the above formulae (Y-1) to (Y-6) is preferably 2 or more. 3 and Y 4 are particularly preferably groups represented by any one of the above formulae (Y-1) to (Y-6). The compound represented by the above formula (2) may have only one type of group represented by the above formulae (Y-1) to (Y-6), or may have two or more types of groups represented by the above formulae (Y-1) to (Y-6).

[0088] X 3 and X 4 is preferably a hydroxyl group, an alkyl group having 1 to 3 carbon atoms, or an alkoxy group having 1 to 3 carbon atoms. Z 2Examples of the alkyl group include a chain hydrocarbon group having 1 to 12 carbon atoms and a valence of (e+f), an alicyclic hydrocarbon group having 3 to 12 carbon atoms and a valence of (e+f), and an aromatic hydrocarbon group having 6 to 12 carbon atoms and a valence of (e+f). 2 is preferably a (e+f)-valent linear or branched chain hydrocarbon group having 1 to 12 carbon atoms, and more preferably a (e+f)-valent linear or branched saturated chain hydrocarbon group having 1 to 10 carbon atoms. From the viewpoint of obtaining a sufficient effect of improving the adhesion between the liquid crystal alignment film and the substrate, a3 and a4 are each preferably 2 or 3. a3+b3 and a4+b4 are each preferably 2 or more, and more preferably 2 to 4. With respect to e and f, e+f is preferably 2 to 6, and more preferably 2 to 4, from the viewpoint of a balance between obtaining a sufficient effect of improving adhesion to a substrate and storage stability.

[0089] By incorporating the compound represented by the above formula (2) as a crosslinking agent into the liquid crystal alignment agent, a liquid crystal alignment film having good adhesion to the substrate can be formed. 3 , Y 4 It is preferable that the specific groups represented by the above formulae (Y-1) to (Y-6) are introduced into the compound in order to form a liquid crystal alignment film having excellent reworkability.

[0090] Specific examples of the compound represented by formula (2) include compounds represented by the following formulas (2-1-1) to (2-1-10). The compound represented by formula (2) may be used alone or in combination of two or more. [ka] [ka]

[0091] The content of the compound [A] in the liquid crystal alignment agent is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, based on 100 parts by mass of the total amount of the polymer components contained in the liquid crystal alignment agent, from the viewpoint of sufficiently increasing the effect of improving adhesion to the substrate. In addition, the content of the compound [A] is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less, based on 100 parts by mass of the total amount of the polymer components contained in the liquid crystal alignment agent, from the viewpoint of suppressing the performance deterioration due to the addition of an excessive amount and from the viewpoint of improving the storage stability. In addition, as the compound [A], one type may be used alone, or two or more types may be used in combination.

[0092] <Other ingredients> The liquid crystal alignment agent of the present disclosure may further contain other compounds other than the polymer component and the compound [A] as necessary. Specific examples thereof include epoxy compounds (e.g., N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, N,N-diglycidyl-aminomethylcyclohexane, 1,6-hexanediol di(meth)acrylate, pentaerythritol tri(meth)acrylate, etc.), functional silane compounds (e.g., 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, etc.), antioxidants, metal chelate compounds, curing accelerators, surfactants, fillers, dispersants, photosensitizers, etc. The content of other compounds can be appropriately selected according to each compound within a range that does not impair the effects of the present disclosure. When a compound different from compound [A] is used in combination as a crosslinking agent, the content of the different compound is preferably 5 mass % or less, more preferably 1 mass % or less, based on the total amount of compound [A] contained in the liquid crystal alignment agent.

[0093] (solvent) The liquid crystal alignment agent of the present disclosure is prepared as a liquid composition in which the polymer component, the compound [A], and any other components that are optionally blended as necessary are preferably dissolved in a solvent. The solvent is preferably an organic solvent, and examples thereof include aprotic polar solvents, phenolic solvents, alcohols, ketones, esters, ethers, halogenated hydrocarbons, and hydrocarbons. Specific examples of the organic solvent to be used include, for example, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,2-dimethyl-2-imidazolidinone, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2-pentanone (diacetone alcohol), ethylene glycol monomethyl ether, butyl lactate, butyl acetate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol-n-propyl ether, ethylene glycol-i-propyl ether, and ethylene glycol-n butyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diisobutyl ketone, isoamyl propionate, isoamyl isobutyrate, diisopentyl ether, ethylene carbonate, propylene carbonate, cyclohexanone, diisobutyl ketone, 3-methoxy-1-butanol, etc. These can be used alone or in combination of two or more.

[0094] The solid content concentration in the liquid crystal alignment agent (the ratio of the total mass of the components other than the solvent of the liquid crystal alignment agent to the total mass of the liquid crystal alignment agent) is appropriately selected in consideration of viscosity, volatility, etc., and is preferably in the range of 1 to 10 mass %. When the solid content concentration is 1 mass % or more, the thickness of the coating film can be sufficiently ensured, and a good liquid crystal alignment film tends to be obtained. On the other hand, when the solid content concentration is 10 mass % or less, the thickness of the coating film does not become too large, and the viscosity of the liquid crystal alignment agent can be appropriately increased, and the coatability tends to be good.

[0095] <Liquid crystal alignment film and liquid crystal element> The liquid crystal alignment film of the present disclosure is formed by the liquid crystal alignment agent prepared as described above. The liquid crystal element of the present disclosure includes a liquid crystal alignment film formed by using the liquid crystal alignment agent described above. The operation mode of the liquid crystal in the liquid crystal element is not particularly limited, and can be applied to various modes such as TN type, STN type, VA type (including VA-MVA type, VA-PVA type, etc.), IPS (In-Plane Switching) type, FFS (Fringe Field Switching) type, OCB (Optically Compensated Bend) type, PSA (Polymer Sustained Alignment) type, etc. The liquid crystal element can be manufactured by a method including, for example, the following steps 1 to 3. In step 1, the substrate used differs depending on the desired operation mode. Steps 2 and 3 are common to each operation mode.

[0096] <Step 1: Formation of coating film> First, a liquid crystal alignment agent is applied onto a substrate, and a coating film is formed on the substrate, preferably by heating the applied surface. As the substrate, for example, a transparent substrate made of glass such as float glass or soda glass; or a resin such as polyethylene terephthalate, polybutylene terephthalate, polyethersulfone, polycarbonate, or poly(alicyclic olefin) can be used. As the transparent conductive film provided on one side of the substrate, a NESA film (registered trademark of PPG, USA) made of tin oxide (SnO2), an ITO film made of indium oxide-tin oxide (In2O3-SnO2), or the like can be used. When manufacturing a TN-type, STN-type, or VA-type liquid crystal element, two substrates on which a patterned transparent conductive film is provided are used. On the other hand, when manufacturing an IPS-type or FFS-type liquid crystal element, a substrate on which an electrode patterned into a comb tooth shape is provided and an opposing substrate on which no electrode is provided are used. The liquid crystal alignment agent is applied to the substrate on the electrode-forming surface, preferably by offset printing, flexographic printing, spin coating, roll coater, or inkjet printing.

[0097] After the liquid crystal alignment agent is applied, preliminary heating (pre-baking) is preferably performed for the purpose of preventing dripping of the applied liquid crystal alignment agent. The pre-baking temperature is preferably 30 to 200°C, and the pre-baking time is preferably 0.25 to 10 minutes. Thereafter, a baking (post-baking) step is performed for the purpose of completely removing the solvent, etc. The baking temperature (post-baking temperature) at this time is preferably 80 to 250°C, more preferably 80 to 200°C. The post-baking time is preferably 5 to 200 minutes. The film thus formed has a thickness of preferably 0.001 to 1 μm.

[0098] <Step 2: Alignment Treatment> When a TN-type, STN-type, IPS-type or FFS-type liquid crystal element is manufactured, a treatment (alignment treatment) is carried out to impart liquid crystal alignment ability to the coating film formed in the above step 1. This imparts the alignment ability of liquid crystal molecules to the coating film, forming a liquid crystal alignment film. As the alignment treatment, a rubbing treatment in which the coating film formed on the substrate is rubbed in a certain direction with a roll wrapped with a cloth made of fibers such as nylon, rayon or cotton, or a photoalignment treatment in which the coating film formed on the substrate is irradiated with light to impart liquid crystal alignment ability to the coating film, can be used. On the other hand, when a vertical alignment (VA) type liquid crystal element is manufactured, the coating film formed in the above step 1 can be used as it is as a liquid crystal alignment film, but in order to further enhance the liquid crystal alignment ability, the coating film may be subjected to an alignment treatment. A liquid crystal alignment film suitable for a vertical alignment type liquid crystal element can also be suitably used for a PSA type liquid crystal element.

[0099] In the photo-alignment treatment, the light irradiation can be performed by a method of irradiating the coating film after the post-bake step, a method of irradiating the coating film after the pre-bake step but before the post-bake step, or a method of irradiating the coating film during heating in at least one of the pre-bake step and the post-bake step. For example, ultraviolet light and visible light containing light with a wavelength of 150 to 800 nm can be used as the radiation to be irradiated to the coating film. Preferably, ultraviolet light containing light with a wavelength of 200 to 400 nm is used. When the radiation is polarized, it may be linearly polarized or partially polarized. When the radiation used is linearly polarized or partially polarized, the irradiation may be performed from a direction perpendicular to the substrate surface, from an oblique direction, or a combination of these. When the radiation is non-polarized, the irradiation direction is an oblique direction.

[0100] Examples of the light source used include a low pressure mercury lamp, a high pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. The radiation dose on the substrate surface is preferably 400 to 50,000 J / m 2 and more preferably 1,000 to 20,000 J / m 2After the light irradiation for imparting the alignment ability, the surface of the substrate may be washed with, for example, water, an organic solvent (e.g., methanol, isopropyl alcohol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, etc.) or a mixture thereof, or the substrate may be heated.

[0101] <Step 3: Construction of liquid crystal cell> Two substrates on which the liquid crystal alignment film is formed as described above are prepared, and a liquid crystal cell is manufactured so that the liquid crystal is disposed adjacent to the liquid crystal alignment film between the two substrates. For example, the liquid crystal cell can be manufactured by disposing two substrates facing each other with a gap therebetween so that the liquid crystal alignment film faces each other, bonding the peripheries of the two substrates with a sealant, injecting liquid crystal into the cell gap surrounded by the substrate surfaces and the sealant, and sealing the injection hole, or by a method using the ODF method. For example, an epoxy resin containing a hardener and aluminum oxide spheres as a spacer can be used as the sealant. For the liquid crystal, nematic liquid crystal and smectic liquid crystal can be mentioned, and among them, nematic liquid crystal is preferred. In the PSA mode, after the liquid crystal cell is constructed, a process is performed in which the liquid crystal cell is irradiated with light while a voltage is applied between the conductive films of a pair of substrates.

[0102] In the case of producing a PSA type liquid crystal element, the liquid crystal element can be produced by a method including the following three steps. A process of applying the liquid crystal aligning agent of the present disclosure onto each conductive film of a pair of substrates having a conductive film to form a coating film. The process of constructing a liquid crystal cell by placing a pair of substrates coated with a liquid crystal alignment agent so that the coating films face each other, sandwiching the liquid crystal layer between them. A process in which light is irradiated onto the liquid crystal cell while a voltage is applied between the conductive films.

[0103] Specifically, a liquid crystal cell is constructed in the same manner as in steps 1 to 3 above, except that a photopolymerizable monomer is injected or dropped together with liquid crystal between a pair of substrates having a conductive film. As the photopolymerizable monomer, a conventionally known compound can be used. A polyfunctional (meth)acrylic monomer is preferable. Thereafter, the liquid crystal cell is irradiated with light while a voltage is applied between the conductive films of the pair of substrates. The voltage applied here can be, for example, 5 to 50 V DC or AC. As the light to be irradiated, for example, ultraviolet light containing light with a wavelength of 150 to 800 nm and visible light can be used. Of these, ultraviolet light containing light with a wavelength of 300 to 400 nm is preferred. As the light source for the irradiated light, for example, a low pressure mercury lamp, a high pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. The amount of light irradiation is preferably 1,000 to 200,000 J / m 2 and more preferably 1,000 to 100,000 J / m 2 It is.

[0104] For each mode of liquid crystal cell, a polarizing plate is then attached to the outer surface of the liquid crystal cell as necessary to form a liquid crystal element. Examples of the polarizing plate include a polarizing film called an "H film" made by absorbing iodine while stretching and aligning polyvinyl alcohol, sandwiched between cellulose acetate protective films, and a polarizing plate made of the H film itself.

[0105] The liquid crystal element of the present disclosure can be effectively applied to various applications, specifically, for example, various display devices such as watches, portable game machines, word processors, notebook computers, car navigation systems, camcorders, PDAs, digital cameras, mobile phones, smartphones, various monitors, liquid crystal televisions, and information displays, as well as light control films, retardation films, and the like. EXAMPLES

[0106] The present invention will be explained in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0107] In the following examples, the solution viscosity, weight average molecular weight (Mw), number average molecular weight (Mn) and imidization rate of the polymer were measured by the following methods. <Polymer solution viscosity> The solution viscosity of the polymer was measured at 25° C. using an E-type viscometer. <Weight average molecular weight and number average molecular weight> Mw and Mn were measured by gel permeation chromatography (GPC) under the following conditions. The molecular weight distribution (Mw / Mn) was calculated from the obtained Mw and Mn. Equipment: Showa Denko Co., Ltd. "GPC-101" GPC column: Shimadzu GLC's "GPC-KF-801", "GPC-KF-802", "GPC-KF-803" and "GPC-KF-804" combined Mobile phase: Tetrahydrofuran (THF) Column temperature: 40℃ Flow rate: 1.0mL / min Sample concentration: 1.0% by mass Sample injection volume: 100 μL Detector: Differential refractometer Standard material: Monodisperse polystyrene <Imidization rate of polyimide> The polyimide solution was poured into pure water, and the resulting precipitate was thoroughly dried under reduced pressure at room temperature. It was then dissolved in deuterated dimethyl sulfoxide and measured at room temperature using tetramethylsilane as a standard substance. 1 H-NMR measurement was performed. 1 The imidization rate [%] was calculated from the H-NMR spectrum using the following formula (1). Imidization rate [%] = (1-(β 1 / (β 2 ×α)))×100 …(1) (In formula (1), β 1 is the peak area due to the proton of the NH group that appears at a chemical shift of around 10 ppm, and β 2 is the peak area due to other protons, and α is the ratio of the number of other protons to one proton of the NH group in the polymer precursor (polyamic acid).

[0108] The abbreviations of the compounds used in the following examples are shown below. For convenience, hereinafter, a "compound represented by formula (X)" may be simply referred to as "compound (X)". Monomers and side chain carboxylic acids [ka] [ka] [ka] [ka] [ka]

[0109] ·Compound [A] [ka] [ka] [ka]

[0110] <Polymer synthesis> 1. Synthesis of Polyimide [Synthesis Example 1] 70 mol parts of 2,3,5-tricarboxycyclopentylacetic dianhydride as tetracarboxylic dianhydride, 30 mol parts of pyromellitic dianhydride, and 30 mol parts of cholestanyloxy-2,4-diaminobenzene as diamine, 40 mol parts of compound (D-4), and 30 mol parts of 3,5-diaminobenzoic acid were dissolved in N-methyl-2-pyrrolidone (NMP) and reacted at 40° C. for 24 hours to obtain a solution containing 20% ​​by mass of polyamic acid. Next, NMP was added to the obtained polyamic acid solution, and pyridine and acetic anhydride were added in amounts of 3.00 molar equivalents each relative to the carboxyl group of the polyamic acid, and a dehydration ring-closing reaction was carried out at 80° C. for 4 hours. After the dehydration ring-closing reaction, the solvent in the system was replaced with new γ-butyrolactone, and the mixture was further concentrated to obtain a solution containing 20% ​​by mass of polyimide with an imidization rate of 63% (referred to as "polymer (P-1)"). A small amount of this solution was taken and NMP was added to make a 10% by mass solution, and the solution viscosity was measured and found to be 37 mPa·s.

[0111] [Synthesis Examples 2, 9-16] Polymerization was carried out in the same manner as in Synthesis Example 1, except that the types and amounts of tetracarboxylic dianhydrides and diamines used in the polymerization were changed as shown in Table 1, to obtain solutions containing the polyimides (P-2) and (P-9) to (P-16).

[0112] 2. Synthesis of polyamic acid [Synthesis Example 3] 70 mol parts of 2,3,5-tricarboxycyclopentylacetic dianhydride and 30 mol parts of 1,2,3,4-cyclobutanetetracarboxylic dianhydride as tetracarboxylic dianhydrides, and 30 mol parts of cholestanyloxy-2,4-diaminobenzene, 40 mol parts of 3,5-diamino-N,N-bis(pyridin-3-ylmethyl)benzamide, and 30 mol parts of 3,5-diaminobenzoic acid as diamines were dissolved in NMP and reacted at 40°C for 24 hours to obtain a solution containing 20% ​​by mass of polyamic acid (referred to as "polymer (P-3)"). A small amount of this solution was taken, and NMP was added to make a solution with a concentration of 10% by mass. The solution viscosity was measured and was 42 mPa·s.

[0113] [Synthesis Examples 4-8, 17] Polymerization was carried out in the same manner as in Synthesis Example 3, except that the types and amounts of tetracarboxylic dianhydrides and diamines used in polymerization were changed as shown in Table 1, to obtain solutions containing the polyamic acid polymers (P-4) to (P-8) and (P-17). In Table 1, the values ​​for the acid anhydrides represent the ratio (molar parts) of each compound relative to 100 parts by mole of the total amount of tetracarboxylic dianhydrides used in the synthesis. The values ​​for the diamines represent the ratio (molar parts) of each compound relative to 100 parts by mole of the total amount of diamines used in the synthesis.

[0114] [Table 1]

[0115] 3. Synthesis of polyorganosiloxane [Synthesis Example 18] In a 1000 ml three-neck flask, 90.0 g of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 500 g of methyl isobutyl ketone, and 10.0 g of triethylamine were charged and mixed at room temperature. Next, 100 g of deionized water was dropped from the dropping funnel over 30 minutes, and then the mixture was reacted at 80 ° C for 6 hours while being mixed under reflux. After the reaction was completed, the organic layer was taken out and washed with a 0.2 mass% aqueous solution of ammonium nitrate until the water after washing became neutral, and then the solvent and water were distilled off under reduced pressure. An appropriate amount of methyl isobutyl ketone was added to obtain a 50 mass% solution of polymer (ESSQ-1), which is a polyorganosiloxane having an epoxy group. In a 500 ml three-neck flask, 6.28 g of compound (C-1) (20 mol% relative to the amount of epoxy groups in the polymer (ESSQ-1)), 3.44 g of compound (C-3) (10 mol% relative to the amount of epoxy groups in the polymer (ESSQ-1)), 2.00 g of tetrabutylammonium bromide, 80 g of the polymer (ESSQ-1)-containing solution, and 239 g of methyl isobutyl ketone were added and stirred at 90 ° C. for 18 hours. After cooling to room temperature, the separation and washing operation with distilled water was repeated 10 times. Thereafter, the organic layer was collected, concentrated by a rotary evaporator and diluted with NMP twice, and then the solid content was adjusted to 10 mass% using NMP to obtain an NMP solution of the polymer (PS-1).

[0116] [Synthesis Example 19] An NMP solution containing 10 mass% of a polyorganosiloxane polymer (PS-2) was obtained in the same manner as in Synthesis Example 18, except that the type and amount of the side chain carboxylic acid used in the reaction were changed as shown in Table 2. In Table 2, the numerical value of the side chain carboxylic acid represents the ratio (side chain modification rate, mol%) to the amount of epoxy groups possessed by the polymer (ESSQ-1).

[0117] [Table 2]

[0118] 4.Synthesis of styrene-maleimide polymers [Synthesis Example 20] Under nitrogen, 10 mol parts of compound (M-1), 10 mol parts of compound (M-4), 35 mol parts of methacrylic acid, and 45 mol parts of glycidyl methacrylate as polymerization monomers, 2 mol parts of 2,2'-azobis(2,4-dimethylvaleronitrile) as a radical polymerization initiator, and 50 ml of tetrahydrofuran as a solvent were added to a 100 mL two-neck flask, and polymerization was carried out at 70 ° C. for 5 hours. After reprecipitation in methanol, the precipitate was filtered and dried in vacuum at room temperature for 8 hours to obtain the target polymer (PM-1). The weight average molecular weight Mw measured in terms of polystyrene by GPC was 30,000, and the molecular weight distribution Mw / Mn was 2.

[0119] [Synthesis Examples 21 and 22] Polymers (PM-2) and (PM-3), which are styrene-maleimide copolymers, were obtained in the same manner as in Synthesis Example 20, except that the types and amounts of the polymerization monomers used in the reaction were changed as shown in Table 3. In Table 3, the numerical values ​​of the monomers indicate the proportion (parts by mole) of each compound used relative to 100 parts by mole of the total amount of the monomers used in the synthesis.

[0120] [Table 3]

[0121] 5. Preparation and evaluation of liquid crystal alignment agent (1) [Example 1: PSA type liquid crystal display element] (1) Preparation of liquid crystal alignment agent (AL-1) 5 parts by mass of compound (Ad-1) and NMP and butyl cellosolve (BC) as a solvent were added to a solution containing 100 parts by mass of polymer (P-1) obtained in Synthesis Example 1 to obtain a solution with a solvent composition of NMP / BC=50 / 50 (mass ratio) and a solid content concentration of 4.0% by mass. This solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal alignment agent (AL-1).

[0122] (2) Reworkability evaluation A liquid crystal alignment agent (AL-1) was applied by a spinner onto a transparent conductive film made of an ITO film provided on one side of a 1 mm thick glass substrate, and pre-baked on a hot plate at 100°C for 90 seconds to form a coating film with a thickness of about 0.10 μm. This operation was repeated to prepare two substrates with a coating film. Next, the two obtained substrates were stored in a dark room at 25°C under a nitrogen atmosphere. After 12 hours and 48 hours from the start of storage, one substrate was taken out and immersed in a beaker containing NMP adjusted to 40°C for 2 minutes, then washed several times with ultrapure water, and water droplets on the surface were removed by air blowing. The substrates were observed by an optical microscope to check for the presence or absence of coating residue, and the ease of peeling the liquid crystal alignment film from the substrate (reworkability) was evaluated. The evaluation was as follows: if no residue of the coating was observed after immersion in NMP, even for a substrate taken out 48 hours after the start of storage, the reworkability was "good (○)", if residue of the coating was observed on the substrate after 48 hours but not on the substrate after 12 hours, the reworkability was "fair (△)", and if residue of the coating was observed on the substrate after 12 hours, the reworkability was "poor (×)". As a result, the reworkability in this example was "good (○)".

[0123] (3) Adhesion evaluation of the film A liquid crystal alignment agent (AL-1) was applied onto a glass substrate using a spinner, prebaked on a hot plate at 80°C for 2 minutes, and then heated (post-baked) for 30 minutes in an oven at 230°C with the interior replaced with nitrogen, forming a coating film with an average thickness of 0.10 μm. By repeating the same operation, two glass substrates with coating films were produced. An ODF sealant (S-WB42, manufactured by Sekisui Chemical Co., Ltd.) was applied to the coating film of one of the glass substrates with a coating film formed thereon to a width of 1 mm, and the other glass substrate was laminated so that the coating film and the ODF sealant were in contact with each other. After that, a metal halide lamp was used to apply 30,000 J / m 2 After irradiating the film with light (converted to 365 nm), the film was heated in an oven at 120°C for 1 hour. The adhesion strength was then measured using a compression and tensile tester (model number: SDWS-0201-100SL) manufactured by Imada Seisakusho, to evaluate the adhesion of the film to the substrate. The evaluation was carried out when the adhesion strength was 175 N / cm2 If it is more than 150N / cm, it is considered to be "Good (○)". 2 More than 175N / cm 2 If it is less than 150N / cm, it is "Fair (△)". 2 If the adhesion was less than 192 N / cm, it was rated as "poor (x)". 2 The adhesion was evaluated as "good (○)."

[0124] (4) Preparation of Liquid Crystal Composition A liquid crystal composition LC1 was obtained by adding and mixing 5% by mass of a liquid crystal compound represented by the following formula (L1-1) and 0.3% by mass of a photopolymerizable compound represented by the following formula (L2-1) to 10 g of a nematic liquid crystal (MLC-6608, manufactured by Merck). [ka]

[0125] (5) Manufacture of PSA type liquid crystal display elements The liquid crystal alignment agent (AL-1) prepared above was applied to each electrode surface of two glass substrates each having a conductive film made of an ITO electrode patterned in a slit shape, using a liquid crystal alignment film printer (manufactured by Nissha Printing Co., Ltd.), heated (pre-baked) for 2 minutes on a hot plate at 80 ° C to remove the solvent, and then heated (post-baked) for 10 minutes on a hot plate at 230 ° C to form a coating film with an average thickness of 0.06 μm. These coating films were ultrasonically cleaned in ultrapure water for 1 minute, and then dried in a clean oven at 100 ° C for 10 minutes to obtain a pair (2 sheets) of substrates having a liquid crystal alignment film. The electrode pattern used was the same type of pattern as the electrode pattern in the PSA mode. Next, an epoxy resin adhesive containing aluminum oxide spheres with a diameter of 5.5 μm was applied to the outer edge of the surface having the liquid crystal alignment film of one of the pair of substrates, and the substrates were then overlapped with the liquid crystal alignment film surfaces facing each other and pressed together, and the adhesive was cured. Next, the liquid crystal composition LC1 prepared above was filled between the pair of substrates through the liquid crystal injection port, and the liquid crystal injection port was sealed with an acrylic photocurable adhesive to produce a liquid crystal cell. Then, an AC voltage of 10 V with a frequency of 60 Hz was applied between the conductive films of the liquid crystal cell, and while the liquid crystal was driven, an ultraviolet irradiation device using a metal halide lamp as a light source was used to irradiate the liquid crystal with 100,000 J / m 2 The substrate was irradiated with ultraviolet light at an exposure dose of 100 μm. The exposure dose was measured using an actinometer with a wavelength of 365 nm as a reference. After that, polarizing plates were attached to both outer surfaces of the substrate so that the polarization directions of the plates were perpendicular to each other and formed an angle of 45° with the projection direction of the optical axis of the ultraviolet light of the liquid crystal alignment film onto the substrate surface, thereby producing a PSA type liquid crystal display element.

[0126] (6) Evaluation of liquid crystal alignment The PSA type liquid crystal display element manufactured above was observed with an optical microscope to see whether there was an abnormal domain in the change in brightness when a voltage of 5V was turned on and off (applied and removed), and the liquid crystal alignment was evaluated as follows: "A" for no abnormal domains, "B" for some abnormal domains, and "C" for the entire abnormal domains. As a result, the liquid crystal alignment in this example was "A".

[0127] (7) Voltage Holding Ratio (VHR) Evaluation A voltage of 5V was applied to the PSA type liquid crystal display element manufactured as above for a time of 60 microseconds over a span of 167 milliseconds, and then the voltage retention rate was measured 167 milliseconds after the application was removed. A VHR-1 manufactured by Toyo Corporation was used as the measuring device. At this time, a voltage retention rate of 98% or more was rated as "S", 95% or more but less than 98% was rated as "A", 80% or more but less than 95% was rated as "B", 50% or more but less than 80% was rated as "C", and less than 50% was rated as "D". As a result, the voltage retention rate in this example was rated as "A".

[0128] [Examples 2, 3, and 5] A liquid crystal alignment agent was prepared with the same solvent composition and solid content concentration as in Example 1, except that the blending composition was changed as shown in Table 4. In addition, using each liquid crystal alignment agent, reworkability and film adhesion were evaluated in the same manner as in Example 1, and a PSA type liquid crystal display element was manufactured to evaluate the liquid crystal alignment property and voltage holding ratio. The results are shown in Table 4. In Table 4, "-" indicates that the compound was not used.

[0129] [Comparative Example 1] A liquid crystal alignment agent (AR-1) was prepared with the same type of polymer, solvent composition and solid content concentration as in Example 1, except that the compound (Ad-1) was not added. In addition, using the prepared liquid crystal alignment agent, reworkability and film adhesion were evaluated in the same manner as in Example 1, and a PSA type liquid crystal display element was manufactured to evaluate the liquid crystal alignment property and voltage holding ratio. The results are shown in Table 4.

[0130] [Example 4: Optical vertical type liquid crystal display element] (1) Preparation of liquid crystal alignment agent and evaluation of reworkability and film adhesion A liquid crystal alignment agent (AL-4) was prepared with the same solvent composition and solid content concentration as in Example 1, except that the blending composition was changed as shown in Table 4. In addition, the liquid crystal alignment agent (AL-4) was used to evaluate reworkability and film adhesion in the same manner as in Example 1. The results are shown in Table 4.

[0131] (2) Manufacturing of vertical optical liquid crystal display elements The liquid crystal alignment agent (AL-4) prepared above was applied to the transparent electrode surface of a glass substrate with a transparent electrode made of an ITO film using a spinner, and pre-baked on a hot plate at 80°C for 1 minute. After that, it was heated at 230°C for 1 hour in an oven with the interior replaced with nitrogen to form a coating film with a thickness of 0.1 μm. Next, the surface of this coating film was irradiated with 1,000 J / m of polarized ultraviolet light containing a 313 nm emission line using a Hg-Xe lamp and a Glan-Taylor prism. 2The substrate was irradiated with light from a direction inclined by 40° from the normal line of the substrate to impart liquid crystal alignment ability. The same procedure was repeated to prepare a pair (two sheets) of substrates having liquid crystal alignment films. An epoxy resin adhesive containing aluminum oxide spheres with a diameter of 3.5 μm was applied by screen printing to the outer circumference of the surface having the liquid crystal alignment film of one of the above substrates, and then the liquid crystal alignment film surfaces of the pair of substrates were placed opposite each other, and pressed together so that the projection directions of the optical axis of the ultraviolet light of each substrate on the substrate surface were antiparallel, and the adhesive was thermally cured at 150°C for 1 hour. Next, the gap between the substrates was filled with negative liquid crystal (MLC-6608, manufactured by Merck) through the liquid crystal injection port, and the liquid crystal injection port was sealed with an epoxy adhesive. Furthermore, in order to remove the flow alignment during the liquid crystal injection, it was heated at 130°C and then slowly cooled to room temperature. Next, polarizing plates were attached to both outer surfaces of the substrate so that the polarization directions were perpendicular to each other and formed an angle of 45° with the projection direction of the optical axis of the ultraviolet light of the liquid crystal alignment film on the substrate surface, thereby manufacturing a vertical light type liquid crystal display element.

[0132] (3) Evaluation of liquid crystal alignment The liquid crystal alignment of the optical vertical type liquid crystal display element manufactured as above was evaluated in the same manner as in Example 1. As a result, in this example, the liquid crystal alignment was evaluated as "A". (4) Voltage Holding Ratio (VHR) Evaluation The voltage holding ratio of the optical vertical type liquid crystal display element manufactured as above was evaluated in the same manner as in Example 1. As a result, the voltage holding ratio of this example was rated "A".

[0133] [Reference examples 1A and 2A] Liquid crystal alignment agents (AR-2) and (AR-3) were prepared with the same solvent composition and solid content concentration as in Example 1, except that compound (Ad-12) or compound (Ad-14) was used instead of compound [A] as an additive, and the blending composition was changed as shown in Table 4. In addition, using each liquid crystal alignment agent, reworkability and film adhesion were evaluated in the same manner as in Example 1, and PSA type liquid crystal display elements were manufactured to evaluate liquid crystal alignment and voltage holding ratio. The results are shown in Table 4.

[0134] [Table 4]

[0135] As shown in Table 4, Examples 1 to 5 containing the compound (Ad-1), (Ad-2) or (Ad-3) had better film adhesion and reworkability than Comparative Example 1 containing no crosslinking agent. Moreover, Examples 1 to 5 were also rated as "A" for the liquid crystal alignment and voltage holding ratio, which were good.

[0136] In addition, in Reference Examples 1A and 2A, in which other crosslinking agents (Ad-12) and (Ad-14) were used instead of Compound [A], the adhesion of the film was good, but the reworkability was poor. Also, Reference Examples 1A and 2A were inferior to Examples 1 to 5 in terms of the voltage holding ratio.

[0137] 6. Preparation and evaluation of liquid crystal alignment agent (2) [Example 6: PSA type liquid crystal display element] (1) Preparation of liquid crystal alignment agent (AL-6) 5 parts by mass of compound (Ad-4) and NMP and butyl cellosolve (BC) as a solvent were added to a solution containing 100 parts by mass of polymer (P-1) obtained in Synthesis Example 1 to obtain a solution with a solvent composition of NMP / BC=50 / 50 (mass ratio) and a solid content concentration of 4.0% by mass. This solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal alignment agent (AL-6).

[0138] (2) Evaluation of film adhesion The liquid crystal alignment agent (AL-6) prepared above was evaluated in the same manner as in "(3) Film Adhesion Evaluation" of Example 1. As a result, in this example, the adhesion was 189 N / cm 2 The result was rated as "good (○)."

[0139] (3) Adhesion evaluation of the film after high-temperature baking The liquid crystal alignment agent (AL-6) prepared in (1) above was applied onto a glass substrate using a spinner, pre-baked for 2 minutes on a hot plate at 80°C, and then heated (post-baked) for 30 minutes in an oven at 300°C with the interior replaced with nitrogen, forming a coating film with an average thickness of 0.10 μm. By repeating the same operation, two glass substrates with coating films were produced. An ODF sealant (S-WB42 manufactured by Sekisui Chemical) was applied to the coating film of one of the glass substrates with the coating film formed thereon to a width of 1 mm, and the other glass substrate was laminated so that the coating film and the ODF sealant were in contact with each other. After that, a metal halide lamp was used to apply 30,000 J / m 2 After irradiating the film with light (converted to 365 nm), the film was heated in an oven at 120°C for 1 hour. The adhesion strength was then measured using a compression and tensile tester (model number: SDWS-0201-100SL) manufactured by Imada Seisakusho, to evaluate the adhesion of the film to the substrate. The evaluation was carried out when the adhesion strength was 175 N / cm 2 If it is more than 160N / cm, it is "particularly good (◎)". 2 More than 175N / cm 2 If it was less than 150N / cm, it was rated as "Good (○)". 2 More than 160N / cm 2 If it is less than 150N / cm, it is "Fair (△)". 2 If the adhesion was less than 190 N / cm, it was rated as "poor (x)". 2 The adhesion was evaluated as "particularly good (A)."

[0140] (4) Manufacture of PSA type liquid crystal display elements A PSA type liquid crystal display element was manufactured in the same manner as in Example 1, except that a liquid crystal alignment agent (AL-6) was used, and the liquid crystal alignment property and the voltage holding ratio were evaluated. As a result, in this example, the liquid crystal alignment property was rated "A", and the voltage holding ratio was rated "S".

[0141] [Examples 7, 8, 10, 11 and Comparative Examples 2 and 3] A liquid crystal alignment agent was prepared with the same solvent composition and solid content concentration as in Example 6, except that the blending composition was changed as shown in Table 5. In addition, using each liquid crystal alignment agent, the adhesion of the film was evaluated in the same manner as in Example 6, and a PSA type liquid crystal display element was manufactured to evaluate the liquid crystal alignment property and voltage holding ratio. The results are shown in Table 5. In Table 5, "-" indicates that the compound was not used.

[0142] [Example 9: Optical vertical type liquid crystal display element] A liquid crystal alignment agent (AL-9) was prepared with the same solvent composition and solid content concentration as in Example 6, except that the blending composition was changed as shown in Table 5. In addition, the liquid crystal alignment agent (AL-9) was used to evaluate the adhesion of the film in the same manner as in Example 6. Furthermore, a vertical light type liquid crystal display element was manufactured in the same manner as in Example 4 using the liquid crystal alignment agent (AL-9), and the liquid crystal alignment property and voltage holding ratio were evaluated. As a result, in this example, the liquid crystal alignment property and voltage holding ratio were rated as "A".

[0143] [Table 5]

[0144] As shown in Table 5, Examples 6 to 11 containing the compound (Ad-4) had better film adhesion and film adhesion after high-temperature baking than Comparative Example 2 containing no crosslinking agent. Moreover, Examples 6 to 11 were also evaluated as "S" or "A" in terms of liquid crystal alignment and voltage holding ratio, which were good.

[0145] In contrast, in Comparative Example 3, in which another crosslinking agent (Ad-12) was used instead of the compound (Ad-4), the adhesion of the film was good when the post-bake temperature was set to 230° C., but was evaluated as poor when the post-bake temperature was set to a high temperature of 300° C. Furthermore, the voltage holding ratio of Comparative Example 3 was also inferior to Examples 6 to 11.

[0146] 7. Preparation and evaluation of liquid crystal alignment agent (3) [Example 12: PSA type liquid crystal display element] (1) Preparation of liquid crystal alignment agent (AL-12) 5 parts by mass of compound (Ad-5) and NMP and butyl cellosolve (BC) as a solvent were added to a solution containing 100 parts by mass of polymer (P-1) obtained in Synthesis Example 1 to obtain a solution with a solvent composition of NMP / BC=50 / 50 (mass ratio) and a solid content concentration of 4.0% by mass. This solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal alignment agent (AL-12).

[0147] (2) Evaluation of film adhesion The liquid crystal alignment agent (AL-12) prepared above was used to evaluate the adhesion of the film in the same manner as in "(3) Evaluation of adhesion of film" in Example 1. As a result, in this example, the adhesion was 191 N / cm 2 The result was rated as "good (○)." (3) Manufacturing and evaluation of PSA type liquid crystal display elements A PSA type liquid crystal display element was manufactured in the same manner as in Example 1, except that a liquid crystal alignment agent (AL-12) was used, and the liquid crystal alignment property and the voltage holding ratio were evaluated. As a result, in this example, the liquid crystal alignment property was rated "A", and the voltage holding ratio was rated "S".

[0148] (4) Evaluation of high temperature and humidity resistance The PSA type liquid crystal display element manufactured at a post-bake temperature of 230°C was stored in an oven set at 60°C and humidity of 90% for 300 hours, and then the voltage holding ratio was measured in the same manner as above. This value was designated as VHR2, and the voltage holding ratio measured before storing under high temperature and high humidity conditions of 60°C and humidity of 90% was designated as VHR1. The reduction amount ΔVHR of the voltage holding ratio was calculated by subtracting VHR1 from VHR2, and the high temperature and high humidity resistance was evaluated based on ΔVHR. When ΔVHR was less than 5%, it was designated as "particularly good (◎)", when it was 5% or more and less than 10%, it was designated as "good (○)", when it was 10% or more and less than 20%, it was designated as "fair (△)", and when it was 20% or more, it was designated as "poor (×)". As a result, in this embodiment, it was "particularly good (◎)".

[0149] [Examples 13, 14, 16, and 17] A liquid crystal alignment agent was prepared with the same solvent composition and solid content concentration as in Example 12, except that the blending composition was changed as shown in Table 6. In addition, using each liquid crystal alignment agent, the adhesion of the film was evaluated in the same manner as in Example 12, and a PSA type liquid crystal display element was manufactured to evaluate the liquid crystal alignment property, voltage holding ratio, and high temperature and high humidity resistance. The results are shown in Table 6. In Table 6, "-" indicates that the compound was not used.

[0150] [Comparative Example 4] A liquid crystal alignment agent (AR-6) was prepared with the same solvent composition and solid content concentration as in Example 12, except that the polymer (P-1) was changed to the polymer (P-15) and the compound (Ad-5) was not added. In addition, the prepared liquid crystal alignment agent was used to evaluate the adhesion of the film in the same manner as in Example 12, and a PSA type liquid crystal display element was manufactured to evaluate the liquid crystal alignment property, voltage holding ratio, and high temperature and high humidity resistance. The results are shown in Table 6.

[0151] [Example 15: Optical vertical type liquid crystal display element] A liquid crystal alignment agent (AL-15) was prepared with the same solvent composition and solid content concentration as in Example 12, except that the blending composition was changed as shown in Table 6. In addition, the liquid crystal alignment agent (AL-15) was used to evaluate the adhesion of the film in the same manner as in Example 12. Furthermore, a vertical light type liquid crystal display element was manufactured in the same manner as in Example 4 using the liquid crystal alignment agent (AL-15), and the liquid crystal alignment property, voltage holding ratio, and high temperature and high humidity resistance were evaluated. As a result, in this example, the liquid crystal alignment property was rated "A" and the voltage holding ratio was rated "S". In addition, the high temperature and high humidity resistance was rated "◎".

[0152] [Example 18: FFS type liquid crystal display element] (1) Preparation of liquid crystal alignment agent and evaluation of film adhesion A liquid crystal alignment agent (AL-18) was prepared with the same solvent composition and solid content concentration as in Example 12, except that the blending composition was changed as shown in Table 6. In addition, the liquid crystal alignment agent (AL-18) was used to evaluate the adhesion of the film in the same manner as in Example 12. The results are shown in Table 6.

[0153] (2) Manufacturing of FFS type liquid crystal display elements The liquid crystal alignment agent (AL-18) prepared above was applied to each of a glass substrate having a flat electrode, an insulating layer, and a comb-shaped electrode laminated in this order on one side and an opposing glass substrate having no electrode, using a spinner, and pre-baked on a hot plate at 80°C for 1 minute. Then, in an oven whose interior was replaced with nitrogen, the substrate was heated at 230°C for 1 hour to form a coating film with a thickness of 0.1 μm. This coating film was subjected to rubbing treatment using a rubbing machine having a roll wrapped with nylon cloth at a roll rotation speed of 1000 rpm, a stage movement speed of 2.5 cm / sec, and a pile indentation length of 0.4 mm. Then, the substrate was ultrasonically cleaned in ultrapure water for 1 minute, and then dried in a clean oven at 100°C for 10 minutes to obtain a substrate having a liquid crystal alignment film. This series of operations was repeated to produce a pair (2 sheets) of substrates having a liquid crystal alignment film. An epoxy resin adhesive containing aluminum oxide spheres with a diameter of 3.5 μm was applied by screen printing to the outer circumference of one of the substrates having a liquid crystal alignment film, and then the substrates were stacked so that the liquid crystal alignment film faces each other, pressed together, and the adhesive was cured. Next, nematic liquid crystal (Merck, MLC-6221) was filled between the pair of substrates through the liquid crystal injection port, which was then sealed with an acrylic photocurable adhesive, and polarizing plates were attached to both outer surfaces of the substrates to produce an FFS type liquid crystal display element.

[0154] (3) Evaluation of liquid crystal alignment, voltage holding ratio and high temperature and humidity resistance The FFS-type liquid crystal display element manufactured in (2) above was evaluated for liquid crystal alignment, voltage holding ratio, and high-temperature, high-humidity resistance in the same manner as in Example 12. As a result, in this example, the liquid crystal alignment was rated "A," the voltage holding ratio was rated "S," and the high-temperature, high-humidity resistance was rated "◎."

[0155] [Reference examples 1B, 2B] Liquid crystal alignment agents (AR-7) and (AR-8) were prepared with the same solvent composition and solid content concentration as in Example 12, except that compound (Ad-12) or compound (Ad-13) was used instead of compound [A] as an additive, and the blending composition was changed as shown in Table 6. In addition, using each liquid crystal alignment agent, the adhesion of the film was evaluated in the same manner as in Example 12, and a PSA type liquid crystal display element was manufactured to evaluate the liquid crystal alignment property, voltage holding ratio, and high temperature and high humidity resistance. The results are shown in Table 6.

[0156] [Table 6]

[0157] As shown in Table 6, Examples 12 to 16 containing the compound (Ad-5) or (Ad-7) had better film adhesion and high temperature and humidity resistance than Comparative Example 4, which did not contain a crosslinking agent. Moreover, Examples 12 to 16 were also good in terms of liquid crystal alignment and voltage holding ratio, with evaluations of "S" or "A."

[0158] In addition, in Reference Examples 1B and 2B in which other crosslinking agents (Ad-12) or (Ad-13) were used instead of the compounds (Ad-5) and (Ad-7), the adhesion of the film was good, but the high temperature and high humidity resistance of the liquid crystal element was poor. Also, Reference Examples 1B and 2B were inferior to Examples 12 to 16 in terms of the voltage holding ratio.

[0159] 8. Preparation and evaluation of liquid crystal alignment agent (4) [Example 19: PSA type liquid crystal display element] (1) Preparation of liquid crystal alignment agent (AL-19) 5 parts by mass of compound (Ad-6) and NMP and butyl cellosolve (BC) as a solvent were added to a solution containing 100 parts by mass of polymer (P-1) obtained in Synthesis Example 1 to obtain a solution with a solvent composition of NMP / BC=50 / 50 (mass ratio) and a solid content concentration of 4.0% by mass. This solution was filtered through a filter with a pore size of 0.2 μm to prepare a liquid crystal alignment agent (AL-19).

[0160] (2) Film adhesion evaluation (seal width 1 mm) The liquid crystal alignment agent (AL-19) prepared above was used to perform an evaluation in the same manner as in "(3) Evaluation of adhesion of film" in Example 1. As a result, in this example, the adhesion was 189 N / cm 2 The result was rated as "good (○)."

[0161] (3) Film adhesion evaluation (seal width 0.5 mm) In "(3) Evaluation of adhesion of film" of Example 1, the adhesion of the film was evaluated in the same manner as in (3) of Example 1, except that the liquid crystal alignment agent (AL-19) prepared above was used and the seal width was changed from 1 mm to 0.5 mm. The evaluation was performed when the adhesion force was 175 N / cm 2 If it is more than 160N / cm, it is "particularly good (◎)". 2 More than 175N / cm 2 If it was less than 150N / cm, it was rated as "Good (○)". 2 More than 160N / cm 2 If it is less than 150N / cm, it is "Fair (△)". 2 If the adhesion was less than 185 N / cm, it was rated as "poor (x)". 2 The result was an evaluation of "particularly good (◎)."

[0162] (4) Manufacture of PSA type liquid crystal display elements A PSA type liquid crystal display element was produced in the same manner as in Example 1, except that a liquid crystal alignment agent (AL-19) was used, and the liquid crystal alignment property and the voltage holding ratio were evaluated. As a result, in this example, the liquid crystal alignment property was rated "A", and the voltage holding ratio was rated "S".

[0163] [Examples 20, 21, 23 to 25, 27 and Comparative Examples 5 to 8] A liquid crystal alignment agent was prepared with the same solvent composition and solid content concentration as in Example 17, except that the blending composition was changed as shown in Table 7. In addition, using each liquid crystal alignment agent, the adhesion of the film was evaluated in the same manner as in Example 19, and a PSA type liquid crystal display element was manufactured to evaluate the liquid crystal alignment property and voltage holding ratio. The results are shown in Table 7. In Table 7, "-" indicates that the compound was not used.

[0164] [Example 22: Optical vertical type liquid crystal display element] A liquid crystal alignment agent (AL-22) was prepared using the same solvent composition and solid content concentration as in Example 19, except that the blending composition was changed as shown in Table 7. In addition, the liquid crystal alignment agent (AL-22) was used to evaluate the adhesion of the film in the same manner as in Example 19. Furthermore, a vertical light type liquid crystal display element was produced in the same manner as in Example 5 using the liquid crystal alignment agent (AL-22), and the liquid crystal alignment property and voltage holding ratio were evaluated. The liquid crystal alignment property of the liquid crystal display element was rated as "good", and the voltage holding ratio was rated as "good".

[0165] [Example 26: FFS type liquid crystal display element] (1) Preparation of liquid crystal alignment agent and evaluation of film adhesion A liquid crystal alignment agent (AL-26) was prepared with the same solvent composition and solid content concentration as in Example 19, except that the blending composition was changed as shown in Table 7. In addition, the liquid crystal alignment agent (AL-26) was used to evaluate the adhesion of the film in the same manner as in Example 19. As a result, in this example, the adhesion of the film was evaluated as "good (○)" when the seal width was 1 mm, and the adhesion of the film was evaluated as "particularly good (◎)" when the seal width was 0.5 mm.

[0166] (2) Evaluation of liquid crystal alignment An FFS-type liquid crystal display element was produced using the liquid crystal alignment agent (AL-26) in the same manner as in Example 18, and the liquid crystal alignment property was evaluated in the same manner as in Example 1. As a result, in this example, the liquid crystal alignment property was "A". (3) Voltage Holding Ratio (VHR) Evaluation An FFS-type liquid crystal display element was produced using the liquid crystal alignment agent (AL-26) in the same manner as in Example 18, and the voltage holding ratio was evaluated in the same manner as in Example 1. As a result, in this example, the voltage holding ratio was rated as "S".

[0167] [Table 7]

[0168] As shown in Table 7, Examples 19 to 27 containing the compounds (Ad-6), (Ad-8) to (Ad-10) had good film adhesion even when the seal width was narrowed to 0.5 mm, compared to Comparative Example 5, which did not contain a crosslinking agent. Furthermore, Examples 19 to 27 were also evaluated as "S" or "A" in terms of liquid crystal alignment and voltage holding ratio, and were good. In contrast, in Comparative Examples 6 to 8, in which other crosslinking agents (Ad-12), (Ad-13) or (Ad-14) were used instead of the compounds (Ad-6), (Ad-8) to (Ad-10), the adhesion of the film was insufficient when the seal width was narrowed, and the film was evaluated as poor. Furthermore, Comparative Examples 6 to 8 were also inferior to Examples 19 to 27 in terms of the voltage holding ratio.

Claims

1. A liquid crystal aligning agent comprising a polymer component and at least one compound [A] selected from the group consisting of compounds represented by the following formula (1) and compounds represented by the following formula (2): 【Chemistry 1】 (In formula (1), Y 1 and Y 2 are each independently a hydrogen atom or a monovalent organic group. 1 and X 2 are each independently a hydroxyl group, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. a1 and a2 are each independently an integer of 1 to 3. b1 and b2 are each independently an integer of 0 to 3, provided that 1≦a1+b1≦5 and 1≦a2+b2≦5 are satisfied. Z 1 is a (c+d)-valent organic group that satisfies the following (i), (ii), or (iii): (i) A (c+d) valent group having 1 to 8 carbon atoms in which at least one hydrogen atom of a saturated chain hydrocarbon group is substituted with a fluorine atom and at least one methylene group of the saturated chain hydrocarbon group is replaced with -O-, or a (c+d) valent group having 2 to 8 carbon atoms in which at least one hydrogen atom of a saturated chain hydrocarbon group is substituted with a carboxyl group. (ii) A (c+d)-valent saturated hydrocarbon group having 11 or more carbon atoms, or a (c+d)-valent aromatic hydrocarbon group having 7 or more carbon atoms, provided that when Z 1 is a (c+d)-valent aromatic hydrocarbon group having 7 or more carbon atoms, Z 1 is represented by "-R 20 -R 22 -R 21 -". R 20 is a single bond or a (c+1)-valent saturated chain hydrocarbon group. R 21 is a single bond or a (d+1)-valent saturated chain hydrocarbon group. R 22 is a group represented by the following formula (r-2-1) or a group represented by the following formula (r-2-2). Provided that the total number of carbon atoms in R 20 , R 21 and R 22 is 7 or more. 【Chemistry 4】 (In formula (r-2-1), R 23 is an alkanediyl group. R 24 is a single bond or an alkanediyl group. R 25 is a monovalent aromatic ring group. In formula (r-2-2), R b is a substituent. t is an integer of 0 to 4. "*" indicates a bond.) (iii) -S- or -SO 2 -. c and d are each independently an integer of 1 to 3. However, in the case of (iii) above, c+d=2. In the case of (ii) above, when R 20 is a single bond, c is 1. When R 21 is a single bond, d is 1. Y 1 , Y 2 , X 1 and X 2 When the same symbol is present multiple times in the formula, the groups having the same symbol are the same or different from each other.) 【Chemistry 2】 (In formula (2), Y 3 and Y 4 are each independently a hydrogen atom or a monovalent organic group. 3 and Y 4 At least one of X is a monovalent group represented by any one of the following formulas (Y-1) to (Y-6). 3 and X 4 are each independently a hydroxyl group, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. a3 and a4 are each independently an integer from 1 to 3. b3 and b4 are each independently an integer from 0 to 3, provided that 1≦a3+b3≦5 and 1≦a4+b4≦5 are satisfied. Z 2 is an organic group having a valence of (e+f). e and f are each independently an integer of 1 to 3. 3 , Y 4 , X 3 and X 4 When the same symbol is present multiple times in the formula, the groups having the same symbol are the same or different from each other.) 【Chemistry 3】 (In formulas (Y-1) to (Y-6), R a and R b are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. "*" indicates a bond.)

2. The polymer component comprises at least one selected from the group consisting of polyamic acid, polyamic acid ester, polyimide, a polymer having a partial structure derived from a monomer having a polymerizable unsaturated bond, and polyorganosiloxane. The liquid crystal alignment agent according to claim 1.

3. The liquid crystal aligning agent according to claim 1 or 2, wherein the polymer component comprises a polymer having a partial structure represented by the following formula (3): *-L 1 -R 1 -R 2 -R 3 -R 4 …(3) (In formula (3), L 1 represents a single bond, -O-, -CO-, -COO-* 1 , -OCO-* 1 , -NR 25 --, --NR 25 -CO-* 1 , —CO—NR 25 -* 1 an alkanediyl group having 1 to 6 carbon atoms, a divalent group in which a hydrogen atom of an alkanediyl group having 2 to 6 carbon atoms is substituted with a hydroxyl group, —O—R 26 -* 1 , or -R 26 -O-* 1 (However, R 25 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. 26 is an alkanediyl group having 1 to 3 carbon atoms. 1 " is R 1 It indicates that it is a bond with . 1 and R 3 R each independently represents a single bond, a substituted or unsubstituted phenylene group, or a substituted or unsubstituted cycloalkylene group. 2 represents a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted cycloalkylene group, or -R 27 -B 1 -R 28 - (However, R 27 and R 28 are each independently a substituted or unsubstituted phenylene group or cycloalkylene group. 1 is a single bond, -O-, -COO-* 2 , -OCO-* 2 , -OCH 2 -* 2 , -CH 2 O-* 2 or an alkanediyl group having 1 to 3 carbon atoms. 2 " is R 28 It indicates that it is a bond with . 4 is a hydrogen atom, a fluorine atom, a cyano group, CH 3 COO-* 3 ("* 3 " is R 3 ), an alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a fluoroalkoxy group having 1 to 18 carbon atoms, a hydrocarbon group having 17 to 51 carbon atoms and a steroid skeleton, or a monovalent group in which a hydrogen atom of an alkyl group or a fluoroalkyl group having 1 to 18 carbon atoms is substituted with a cyano group. 1 , R 2 and R 3 are all single bonds, or R 1 , R 2 and R 3 When the total number of substituted or unsubstituted phenylene groups and cycloalkylene groups contained in R is 1, 4 is an alkyl group having 4 to 18 carbon atoms, a fluoroalkyl group having 4 to 18 carbon atoms, an alkoxy group having 4 to 18 carbon atoms, a fluoroalkoxy group having 4 to 18 carbon atoms, or a hydrocarbon group having a steroid skeleton and 17 to 51 carbon atoms. "*" indicates a bond.)

4. The polymer component is at least one selected from the group consisting of polyamic acid, polyamic acid ester, and polyimide, and 4 -NR 11 R 12 "," * 4 -NR 13 -* 5 "," * 4 -NR 14 -CO-NR 15 -* 5 "," * 4 -NR 16 -CO-* 5 " and "* 4 -COOR 17 ” (However, R 11 R is a hydrogen atom or a monovalent organic group. 12 is a protecting group. 13 ~R 17 are each independently a hydrogen atom or a protecting group. 4 " and "* 5 " indicates a bond to a carbon atom constituting a carbon-carbon bond.) The liquid crystal aligning agent according to any one of claims 1 to 3, comprising a polymer having a structural unit derived from a diamine having at least one partial structure selected from the group consisting of:

5. A liquid crystal alignment film formed by using the liquid crystal aligning agent according to any one of claims 1 to 4.

6. A liquid crystal device comprising the liquid crystal alignment film according to claim 5 .

7. A step of applying the liquid crystal aligning agent according to any one of claims 1 to 4 onto each of the conductive films of a pair of substrates having a conductive film to form a coating film; A step of constructing a liquid crystal cell by disposing a pair of substrates coated with the liquid crystal alignment agent such that the coating films face each other with a liquid crystal layer therebetween; applying a voltage between the conductive films and irradiating the liquid crystal cell with light; A method for manufacturing a liquid crystal element, comprising:

Citation Information

Patent Citations

  • Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element

    WO2010074269A1

  • Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element using same

    WO2020162462A1

  • Liquid crystal alignment agent, liquid crystal alignment film and liquid crystal display element using same

    WO2020184629A1